Two-component (2k) curable adhesive composition

By developing two parts (2K) adhesive compositions that include (methyl) acrylate monomers, common polycons, and electrolytes, the existing adhesives are solved. The problem of poor sexual and difficult to remove adhesion realizes the effective decapyles caused by stable adhesion and electrostatic difference under high temperature and high humidity conditions.

CN119384437APending Publication Date: 2025-01-28HENKEL KGAA
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
CN202380047018.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-05-16
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing adhesives are difficult to maintain adhesive stability under high temperature and high humidity conditions, and are difficult to effectively debond when disassembly is required, and commonly used methods may damage the substrate.

Method used

A two -part part (2K) adhesive composition that can be cured and sticky, including (methyl) acrylate monomer, common polycic acid, electrolyte, first curing agent, second curing agent, wax, and The solvent is weakened by applying a voltage to make the adhesive adhesive part of the adhesive part, thereby achieving desertation.

Benefits of technology

Provide excellent adhesive stability under high temperature and high humidity conditions, and achieve effective removal adhesion through the difference in potential to avoid damage to the substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384437A_ABST
    Figure CN119384437A_ABST
Patent Text Reader

Abstract

The present invention relates to a curable and debondable two part (2K) adhesive composition, the curable and debondable two part (2K) adhesive composition comprising: i) a first part, the first part comprising: a (meth) acrylate monomer; a copolymerizable acid; and an electrolyte; and ii) a second portion comprising: a first curing agent for the monomers of the first portion; a second curing agent for the monomers of the first portion; wax; the two-part (2K) binder composition further comprises a toughening agent, a deoxidant and a rheology control agent, and further wherein the two-part (2K) binder composition is characterized in that the electrolyte comprises or consists of at least one salt according to formula (I) or formula (II): # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to adhesive compositions that can be debonded from a particular substrate to which it is applied. More particularly, the present invention relates to two-part (2K) curable and debondable adhesive compositions that are particularly useful in the bonding of electronic components. Background Art

[0002] Adhesive bonding and polymer coatings are commonly used in the assembly and finishing of manufactured products. They are used to replace mechanical fasteners such as screws, bolts, and rivets to provide bonding at reduced machine costs and greater applicability in the manufacturing process. Adhesive bonding distributes stress evenly, reduces the potential for fatigue, and seals joints from corrosive substances.

[0003] While adhesive bonding thus provides many advantages over mechanical fasteners, adhesive bonded items tend to be difficult to disassemble when necessary in practical applications. Removal of adhesives by mechanical methods (such as by sandblasting or by wire brushing) is generally excluded, in part because the adhesive is disposed between the substrates and is therefore difficult to access or difficult to polish without damaging the substrate surface. Disassembly by application of chemicals and / or high temperatures (as disclosed in U.S. Pat. No. 4,171,240 (Wong), U.S. Pat. No. 4,729,797 (Linde et al.), and US20140287299 A1 (Krogdahl)) may be effective, but can be time-consuming and complicated to perform; in addition, the aggressive chemicals and / or harsh conditions required can damage the separated substrates, making them unsuitable for subsequent applications.

[0004] As an exemplary case, it is clearly desirable to remove, replace and / or recycle components of electronic devices (such as personal computers, laptops and tablet computers) that have been attached within the device using adhesives. However, such adhesives are generally robust because they are designed to maintain adhesion during drops or shock events and over a wide range of operating temperatures and other environmental conditions. If care is not taken, adhesive-bonded device components may be damaged or destroyed when the components are removed by mechanical means, application of chemicals or high temperatures.

[0005] With these problems in mind, some authors have attempted to develop debondable adhesive compositions in which an electrical current is passed through the cured composition to disrupt the bond at the interface of the adhesive with the substrate.

[0006] U.S. Pat. No. 7,465,492 (Gilbert) describes a debondable composition comprising: a matrix functional group comprising a monomer selected from the group consisting of acrylics, methacrylics, and combinations thereof; a free radical initiator; and an electrolyte, wherein the electrolyte provides sufficient ionic conductivity to the composition to support a faradaic reaction at a bond formed between the composition and a conductive surface and thereby debond the composition from the surface.

[0007] US2007 / 0269659 (Gilbert) describes an adhesive composition that is debondable at two interfaces, which composition: (i) comprises a polymer and an electrolyte; (ii) promotes bonding of the two surfaces; and (iii) responds to a voltage applied across the two surfaces to form an anodic interface and a cathodic interface, thereby debonding from both the anodic surface and the cathodic surface.

[0008] US2008 / 0196828 (Gilbert) describes a hot melt adhesive composition comprising: a thermoplastic component; and an electrolyte, wherein the electrolyte provides sufficient ionic conductivity to the composition to enable a Faradaic reaction at a bond formed between the composition and a conductive surface and to debond the composition from the surface.

[0009] WO2017 / 133864 (Henkel AG & Co. KGaA) describes a method for reversibly bonding a first substrate and a second substrate, wherein at least the first substrate is a non-conductive substrate, the method comprising: a) coating the surface of one or more non-conductive substrates with a conductive ink; b) applying an electrically debondable hot melt adhesive composition to the surface of the first substrate coated with the conductive ink and / or the second substrate; c) contacting the first substrate with the second substrate so that the electrically debondable hot melt adhesive composition is sandwiched between the two substrates; d) forming an adhesive bond between the two substrates to provide a bonded substrate; and e) applying a voltage to the bonded substrates, whereby the adhesion at at least one interface between the electrically debondable hot melt adhesive composition and the substrate surface is substantially weakened.

[0010] EP 3835381 A1 (Henkel AG & Co. KGaA) describes a curable and debondable two-part (2K) adhesive composition comprising: i) a first part comprising: a (meth)acrylate monomer; a copolymerizable acid; and an electrolyte; and ii) a second part comprising: a first curing agent for the monomers of the first part; a second curing agent for the monomers of the first part; and a solubilizer.

[0011] The art still needs to provide an adhesive composition, which can be easily applied to the surface of a substrate to be bonded, and after it is cured, effective bonding can be provided in a composite structure containing the substrate, but can be effectively debonded from those substrates by easily applying an electric potential across the cured adhesive. In particular, the inventor has recognized that the art needs to develop a debondable adhesive, which can be applied to the surface of a substrate to be bonded without degrading the bonding portion in the composite structure when those substrates are exposed to high humidity and high temperature conditions. Such a debondable adhesive has a favorable utility especially in electronic devices. Summary of the invention

[0012] According to a first aspect of the present invention, there is provided a curable and debondable two-part (2K) adhesive composition, the curable and debondable two-part (2K) adhesive composition comprising:

[0013] The first part (A), wherein the first part (A) comprises:

[0014] (Meth)acrylate monomers;

[0015] Copolymerizable acids; and

[0016] Electrolytes; and

[0017] The second part (B), wherein the second part (B) comprises:

[0018] a first curing agent for the monomers of the first portion;

[0019] a second curing agent for the monomers of the first portion;

[0020] wax; and

[0021] Solubilizer,

[0022] wherein the two-part (2K) adhesive composition further comprises:

[0023] Toughening agent;

[0024] Oxygen scavengers; and

[0025] Rheology control agents;

[0026] Further wherein the two-part (2K) adhesive composition is characterized in that the electrolyte comprises or consists of at least one salt according to formula (I) or formula (II):

[0027]

[0028] Where: R 1 , R 2 , R3 , R 4 and R 5 are independently selected from hydrogen, C 1 -C 18 Alkyl, C 3 -C 18 Cycloalkyl, C 6 -C 18 Aryl, C 7 -C 24 Aralkyl, C 2 -C 20 Alkenyl, -C(O)R q , -C(O)OH, -CN, or -NO 2 ; and R q It is C 1 -C 6 alkyl;

[0029] and

[0030] X - is a counter anion selected from the group consisting of:

[0031]

[0032] The formula R a Japanese R b are independently selected from hydrogen, C 1 -C 12 Alkyl, C 5 -C 12 Cycloalkyl, C 5 -C 12 Heterocycloalkyl, C 6 -C 18 Aryl, or C 5 -C 18 Heteroaryl.

[0033] Tougheners, oxygen scavengers and rheology control agents may be included in one or both of said parts of the composition. However, it is preferred that the first component of the composition comprising the reactive monomers also comprises said tougheners, oxygen scavengers and rheology control agents.

[0034] In an important embodiment of the present invention, the two-part adhesive composition comprises:

[0035] A first part (A), based on the weight of the first part, the first part (A) comprises:

[0036] 20-80 wt%, preferably 30-60 wt% of the (meth)acrylate monomer;

[0037] 0.5-20 wt%, preferably 5-15 wt% of the copolymerizable acid; and

[0038] 0.5-20 wt%, preferably 5-15 wt% of said electrolyte; and

[0039] A second part (B), based on the weight of the second part, the second part (B) comprises:

[0040] 5-40 wt %, preferably 10-40 wt % of the first curing agent;

[0041] 0.01-2 wt %, preferably 0.01-1 wt % of the second curing agent;

[0042] 5-30 wt%, preferably 5-20 wt% of said wax; and

[0043] 20-60 wt. %, preferably 30-60 wt. % of said solubilizing agent,

[0044] Wherein, based on the total weight of the composition, the composition further comprises:

[0045] 5-40 wt%, preferably 10-40 wt% of the toughening agent;

[0046] 0.1-5 wt%, preferably 0.1-2 wt% of the oxygen scavenger; and

[0047] 1-20 wt% of said rheology control agent.

[0048] The first part (A) and the second part (B) are conventionally combined in an A:B weight ratio of 20:1 to 1:1 (e.g., 15:1 to 5:1, or 12:1 to 8:1). Particularly preferred embodiments of the composition have a weight ratio of Part A:Part B of 10:1.

[0049] Compositions according to these definitions have been demonstrated to provide excellent bond stability under conditions of high temperature and humidity, with the examples below demonstrating particular stability at 95% relative humidity (RH) and 65° C. Furthermore, when composite structures have been formed using the cured adhesive compositions, these structures are readily debonded by applying a potential difference across the adhesive bond.

[0050] In the first part of the adhesive composition, the copolymerizable acid is preferably selected from methacrylic acid, acrylic acid, itaconic acid, maleic acid, aconitic acid, crotonic acid, fumaric acid, and mixtures thereof: note that methacrylic acid is particularly preferred.

[0051] Independently or in addition to this preferred statement about the copolymerizable acid of the first part, the electrolyte is preferably selected from: 1-methylimidazolium bis(trifluoromethylsulfonyl)imide; 3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-butyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide; 1-hexyl- 3-Methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-octyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-methyl-3-octylimidazolium bis(trifluoromethylsulfonyl)imide; 1-decyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; tetraethylphosphonium bis(trifluoromethylsulfonyl)imide; tetrabutylphosphonium bis(trifluoromethylsulfonyl)imide; tridecyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide; and mixtures thereof. There may be mentioned as particularly preferred use of at least one of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide.

[0052] In the second part of the adhesive composition, it is preferred that the first curing agent is a peroxide curing agent, and the peroxide curing agent is preferably selected from tert-butyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, tert-butyl perbenzoate, diacetyl peroxide, benzoyl peroxide, tert-butyl peracetate, lauryl peroxide, and mixtures thereof: benzoyl peroxide is particularly preferred.

[0053] Independently or additionally to this preferred statement about the first curing agent, the second curing agent preferably consists of at least one compound which is a salt or coordination compound of a transition metal selected from Fe, Co, V, Mn and Cu. More preferably, the second curing agent comprises or consists of at least one iron-based compound selected from ferrocene, iron (II) acetylacetonate, and hexa(cyano-C)ferrate (4-) iron (3+) ammonium.

[0054] Independently or additionally to the preferred statements about the first curing agent and the second curing agent, it is preferred that the solubilizer of the second part of the adhesive composition is a polyalkylene glycol or an epoxy resin, wherein the epoxy resin is selected from alicyclic epoxy compounds, epoxy novolac resins, bisphenol A epoxy resins, bisphenol F epoxy resins, epoxy resins based on bisphenol A epichlorohydrin, alkyl epoxy compounds, limonene dioxide, polyepoxides, and mixtures thereof; note that a solubilizer containing or consisting of a bisphenol A epoxy resin is particularly preferred.

[0055] According to a second aspect of the present invention, there is provided a bonded structure comprising:

[0056] a first material layer having a conductive surface; and

[0057] a second material layer having a conductive surface,

[0058] A cured debondable two-part (2K) adhesive composition as defined above and in the appended claims is disposed between the first material layer and the second material layer.

[0059] According to a third aspect of the present invention there is provided a method of debonding a bonded structure as defined above and in the appended claims, the method comprising the steps of:

[0060] i) applying a voltage across the two surfaces to form an anodic interface and a cathodic interface; and

[0061] ii) Debonding the surface.

[0062] Step i) of the method is preferably characterized by at least one of the following:

[0063] a) an applied voltage of 0.5-100 V; and

[0064] b) The voltage is applied for a duration ranging from 1 second to 60 minutes.

[0065] definition

[0066] As used herein, the singular forms "a", "an", and "the" include plural referents unless the context clearly dictates otherwise.

[0067] As used herein, the terms "comprising / comprises / comprised of" are synonymous with "including / includes" or "containing / contains", are inclusive or open-ended, and do not exclude additional unrecited members, elements, or method steps.

[0068] As used herein, the term "consisting of excludes any elements, ingredients, members, or method steps not specified.

[0069] When amounts, concentrations, sizes and other parameters are expressed in the form of ranges, preferred ranges, upper values, lower values, or preferred upper and lower values, it should be understood that any range obtainable by combining any upper value or preferred value with any lower value or preferred value is also specifically disclosed, regardless of whether the obtained range is explicitly mentioned in the context.

[0070] Furthermore, according to standard understanding, weight ranges expressed as "0-x / 0 to x" specifically include 0 wt %: the ingredient defined by the range may not be present in the composition or may be present in the composition in an amount of up to x wt %.

[0071] The words "preferred / preferably", "desirable", and "particularly / especially" are generally used herein to refer to embodiments of the present disclosure that may provide particular benefits in certain circumstances. However, the recitation of one or more preferred, preferred, desirable, or particular embodiments does not mean that other embodiments are not useful, and is not intended to exclude those other embodiments from the scope of the present disclosure.

[0072] As used throughout this application, the words "may" are used in a permissive sense (ie, meaning having the potential to), rather than in a mandatory sense.

[0073] As used herein, room temperature is 23° C.±2° C. As used herein, “ambient conditions” means the temperature and pressure of the environment to which a composition is exposed or to which a coating or substrate of the coating is exposed.

[0074] A "two-part (2K) composition" in the context of the present invention is understood to be a composition in which the first part (A) and the second part (B) have to be stored in separate containers due to their (high) reactivity. The two parts are mixed only shortly before application and then react, usually without additional activation, with bond formation and thus formation of a polymer network. In this context, higher temperatures can be applied in order to accelerate the crosslinking reaction.

[0075] As used herein, the term "debondable" means that after the adhesive is cured, the bond strength can be weakened by at least 50% after applying a potential of 5V to 75V for a duration of 1 second to 60 minutes. The cured adhesive is applied between two substrates bonded by the adhesive so that an electric current flows through the adhesive bonding layer. The bond strength is measured by a tensile lap shear (TLS) test performed at room temperature based on EN1465:2009 (German version) based on the determination of tensile lap shear strength of adhesive-bonded assemblies.

[0076] As used herein, the term "monomer" refers to a substance that can undergo a polymerization reaction to provide a building block for the chemical structure of a polymer. As used herein, the term "monofunctional" refers to having one polymerizable moiety. As used herein, the term "multifunctional" refers to having more than one polymerizable moiety.

[0077] As used herein, the term "equivalent" (eq.) refers, as usual in chemical notation, to the relative quantity of reactive groups present in a reaction.

[0078] The term "electrolyte" is used herein according to its standard meaning in the art as a substance containing free ions that can conduct electricity by displacement of charge carrier species. The term is intended to encompass molten electrolytes, liquid electrolytes, semisolid electrolytes, and solid electrolytes in which at least one of the cationic or anionic components of the electrolyte structure is substantially free to displace, thereby acting as a charge carrier.

[0079] The curable adhesive composition of the present invention and the cured adhesive obtained therefrom have "electrolyte function" because the adhesive material allows the conduction of ions (anions, cations, or both anions and cations). The electrolyte function is understood to be derived from the ability of the composition and the cured adhesive to solvate ions of at least one polarity.

[0080] As used herein, "(meth)acryl" is a shorthand term for "acryl" and / or "methacryl." Thus, the term "(meth)acrylamide" refers collectively to acrylamide and methacrylamide.

[0081] As used herein, “C 1 -C n An "alkyl" group refers to a monovalent group containing 1 to n carbon atoms, which is a radical of an alkane and includes straight-chain and branched organic groups. Thus, an "alkyl" group refers to a monovalent group containing 1 to n carbon atoms, which is a radical of an alkane and includes straight-chain and branched organic groups. 1 -C 18An "alkyl" group refers to a monovalent group containing 1 to 18 carbon atoms, which is a radical of an alkane and includes straight-chain and branched organic groups. Generally, it should be noted that for alkyl groups containing 1 to 12 carbon atoms (C 1 -C 12 Alkyl) (e.g., an alkyl group containing 1 to 8 carbon atoms (C 1 -C 8 Examples of alkyl groups include, but are not limited to, methyl; ethyl; propyl; isopropyl; n-butyl; isobutyl; sec-butyl; tert-butyl; n-pentyl; n-hexyl; n-heptyl; and 2-ethylhexyl. In the present invention, such alkyl groups may be unsubstituted or may be substituted with one or more halogens. When applicable to a given portion (R), the specification will indicate the tolerance for one or more non-halogen substituents in the alkyl group.

[0082] As used herein, the term “C 1 -C 18 "Hydroxyalkyl" refers to a HO-(alkyl) group having 1-18 carbon atoms, wherein the point of attachment of the substituent is through the oxygen atom and alkyl is as defined above.

[0083] "Alkoxy" refers to a monovalent group represented by -OA, where A is an alkyl group: non-limiting examples of which are methoxy, ethoxy, and isopropoxy. As used herein, the term "C 1 -C 18 "Alkoxyalkyl" refers to an alkyl group having an alkoxy substituent as defined above and wherein the moiety (alkyl-O-alkyl) contains 1 to 18 carbon atoms in total: such groups include methoxymethyl (-CH 2 OCH 3 )、2-methoxyethyl (-CH 2 CH 2 OCH 3 ) and 2-ethoxyethyl. Similarly, as used herein, the term "C 7 -C 18 "Alkoxyaryl" refers to an aryl group having an alkoxy substituent as defined above and wherein the portion (aryl-O-alkyl) has 7 to 18 carbon atoms in total.

[0084] As used herein, the term “C 2 -C 4 "Alkylene" is defined as a saturated divalent hydrocarbon radical having 2 to 4 carbon atoms.

[0085] The term "C 3 -C 18"Cycloalkyl" should be understood to mean a saturated monocyclic or polycyclic hydrocarbon radical having 3 to 18 carbon atoms. In the present invention, such cycloalkyl groups may be unsubstituted or may be substituted by one or more halogens. When applicable to a given moiety (R), the specification will indicate the tolerance for one or more non-halogen substituents in the cycloalkyl group. Examples of cycloalkyl groups include: cyclopropyl; cyclobutyl; cyclopentyl; cyclohexyl; cycloheptyl; cyclooctyl; adamantane; and norbornane.

[0086] As used herein, "C" used alone or as part of a larger moiety (such as in "aralkyl") 6 -C 18 "Aryl" refers to monocyclic, bicyclic and tricyclic ring systems, wherein the monocyclic ring system is aromatic or at least one of the rings in the bicyclic or tricyclic ring system is aromatic. Bicyclic and tricyclic ring systems include benzo-fused 2-3 membered carbon rings. In the present invention, such aryl groups may be unsubstituted or substituted with one or more halogens. When applicable to a given moiety (R), the specification will indicate the tolerance for one or more non-halogen substituents in the aryl group. Exemplary aryl groups include: phenyl; (C 1 -C 4 ) alkylphenyl such as tolyl and ethylphenyl; indenyl; naphthyl, tetrahydronaphthyl, tetrahydroindenyl; tetrahydroanthracenyl; and anthracenyl. In addition, preference for phenyl may be noted.

[0087] As used herein, “C 2 -C 20 "Alkenyl" refers to a hydrocarbon group having 2-20 carbon atoms and at least one ethylenically unsaturated unit. The alkenyl group may be linear, branched or cyclic, and may be optionally substituted with one or more halogens. When applicable to a given portion (R), the specification will indicate the tolerance of one or more non-halogen substituents in the alkenyl group. As understood by those of ordinary skill in the art, the term "alkenyl" also includes groups having "cis" and "trans" configurations, or alternatively "E" and "Z" configurations. However, in general, it should be noted that for alkenyl groups containing 2-10 carbon atoms (C 2-10 ) or contains 2-8 carbon atoms (C 2-8 ) is preferably an unsubstituted alkenyl. 2 -C 12 Examples of alkenyl groups include, but are not limited to: —CH═CH 2 ; —CH═CHCH 3 ;—CH 2 CH═CH 2 ; —C(═CH 2 )(CH 3 ); —CH═CHCH 2 CH3 ;—CH 2 CH═CHCH 3 ;—CH 2 CH 2 CH═CH 2 ; —CH═C(CH 3 ) 2 ;—CH 2 C(═CH 2 )(CH 3 );—C(═CH 2 )CH 2 CH 3 ;—C(CH 3 )═CHCH 3 ;—C(CH 3 )CH═CH 2 ; —CH═CHCH 2 CH 2 CH 3 ;—CH 2 CH═CHCH 2 CH 3 ;—CH 2 CH 2 CH═CHCH 3 ;—CH 2 CH 2 CH 2 CH═CH 2 ; —C(═CH 2 )CH 2 CH 2 CH 3 ;—C(CH 3 )═CHCH 2 CH 3 ;—CH(CH 3 )CH═CHCH; —CH(CH 3 )CH 2 CH═CH 2 ;—CH 2 CH═C(CH 3 ) 2 ; 1-cyclopent-1-enyl; 1-cyclopent-2-enyl; 1-cyclopent-3-enyl; 1-cyclohex-1-enyl; 1-cyclohex-2-enyl; and 1-cyclohexyl-3-enyl.

[0088] As used herein, "alkylaryl" refers to an aryl group substituted by an alkyl group, both groups being as defined above. Additionally, as used herein, "aralkyl" means an alkyl group substituted by an aryl group as defined above.

[0089] As used herein, the term "hetero" refers to a group or moiety that contains one or more heteroatoms such as N, O, Si and S. Thus, for example, "heterocycle" refers to a cyclic group having, for example, N, O, Si or S as part of the ring structure. "Heteroalkyl", "heterocycloalkyl" and "heteroaryl" moieties are alkyl, cycloalkyl and aryl groups, respectively, as defined above, containing N, O, Si or S as part of their structure.

[0090] As used herein, the term "equivalent weight" refers to the molecular weight divided by the number of functional groups involved. Thus, "epoxy equivalent weight" (EEW) means the weight (in grams) of a resin containing one equivalent of epoxy groups.

[0091] As used herein, the term "epoxide" means a compound characterized by the presence of at least one cyclic ether group, i.e., a compound in which an ether oxygen atom is connected to two adjacent carbon atoms to form a cyclic structure. The term is intended to include monoepoxides, polyepoxides (having two or more epoxy groups), and epoxy-terminated prepolymers. The term "monoepoxide" is intended to mean an epoxy compound having one epoxy group. The term "polyepoxide" is intended to mean an epoxy compound having at least two epoxy groups. The term "diepoxide" is intended to mean an epoxy compound having two epoxy groups.

[0092] The epoxy compound may be unsubstituted, but may also be inertly substituted. Exemplary inert substituents include chlorine, bromine, fluorine and phenyl.

[0093] Molecular weights referred to in this specification may be measured using gel permeation chromatography (GPC) using polystyrene calibration standards, such as performed according to ASTM 3536.

[0094] As used herein, the term softening point (° C.) used herein with respect to waxes is the ring and ball softening point, which is measured according to ASTM E28 unless otherwise indicated.

[0095] Unless otherwise specified, the viscosity of the compositions described herein is measured using an Anton Paar viscometer (model MCR 301) at standard conditions of 25°C and 50% relative humidity (RH). The viscometer is calibrated once a year and checked by the service department. The calibration is performed using special oils of known viscosity, which vary from 5,000 cps to 50,000 cps (parallel plate PP25, shear rate of 1 s -1 , 23° C.). The compositions according to the invention are measured using a parallel plate PP20 at 1.5 to 100 s -1 was carried out at different shear rates. DETAILED DESCRIPTION

[0096] First part of a two-part (2K) composition

[0097] The first part of a two-part (2K) composition necessarily comprises: a (meth)acrylate monomer; a copolymerizable acid; and an electrolyte.

[0098] (Meth)acrylate monomer

[0099] The first part of the composition comprises (meth)acrylate monomers which will typically be present in an amount of 20-80 wt% based on the weight of the first part: preferably, the (meth)acrylate monomers comprise 30-60 wt%, for example 35-50 wt% of the first part.

[0100] These (meth)acrylate monomer amounts are preferred because an amount greater than 80% adversely affects initial adhesive properties and debonding effects, whereas a low amount (mainly less than 20%) results in reduced initial adhesive properties.

[0101] It is not intended to specifically limit the (meth)acrylates that can be used herein, and it is contemplated that the (meth)acrylate monomers can be any ester of acrylic acid or methacrylic acid known in the art. That is, exemplary (meth)acrylic monomers include, but are not limited to:

[0102] ·(Meth)acrylic acid C 1 -C 18 Alkyl esters, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate (all isomers), hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate and n-octadecyl (meth)acrylate;

[0103] ·(Meth)acrylic acid C 3 -C 18 Cycloalkyl esters, such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate;

[0104] ·(Meth)acrylic acid C 6 -C 18 Aryl esters, such as phenyl (meth)acrylate and toluene (meth)acrylate;

[0105] ·(Meth)acrylic acid C 7 -C 24 Arylalkyl esters, such as benzyl (meth)acrylate;

[0106] ·(Meth)acrylic acid C 1 -C 18 Alkoxyalkyl esters, such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, and 3-methoxybutyl (meth)acrylate;

[0107] Fluorinated C of (meth)acrylic acid 1 -C 18 Alkyl esters such as trifluoromethyl methyl (meth)acrylate, 2-trifluoromethyl ethyl (meth)acrylate, 2-perfluoroethyl ethyl (meth)acrylate, 2-perfluoroethyl-2-perfluorobutylethyl (meth)acrylate, 2-perfluoroethyl (meth)acrylate, perfluoromethyl (meth)acrylate, diperfluoromethyl methyl (meth)acrylate, 2-perfluoromethyl-2-perfluoroethyl methyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate and 2-perfluorohexadecylethyl (meth)acrylate;

[0108] ·(Meth)acrylic acid C 1 -C 18 Hydroxyalkyl esters, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate and pentaerythritol tri(meth)acrylate;

[0109] Diesters / polyesters of difunctional / polyfunctional alcohols, such as ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate or 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate and trimethylolpropane tri(meth)acrylate;

[0110] ·(Meth)acrylic acid C 1 -C 18 Aminoalkyl esters such as 2-aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate and (meth)acryloyloxyethoxyethylamine;

[0111] ·(Meth)acrylic acid containing C 1 -C 18 Alkyl esters of alkoxysilyl groups, such as γ-(methacryloxypropyl)trimethoxysilane;

[0112] ethylene oxide or propylene oxide adducts of (meth)acrylic acid; and

[0113] (Meth)acrylates formed from alcohols with other functional groups, such as tetrahydrofurfuryl (meth)acrylate.

[0114] For the sake of completeness, it is not excluded that the first part of the composition comprises a macromer component consisting of one or more oligomers selected from urethane (meth)acrylates, polyester (meth)acrylates and polyether (meth)acrylates. However, such oligomeric compounds, which may be monofunctional or polyfunctional with respect to the polymerizable (meth)acrylate functional groups but are based on repeating structural urethane, ester and ether subunits, should generally not represent more than 30% by weight of all (meth)acrylate monomers in the first part.

[0115] As known in the art, urethane (meth)acrylate oligomers can be prepared by reacting a multifunctional (meth)acrylate carrying a hydroxyl group with a polyisocyanate as defined above. In particular, the multifunctional (meth)acrylate carrying a hydroxyl group can be selected from: 2-hydroxyethyl (meth)acrylate; 2-hydroxyisopropyl (meth)acrylate; 4-hydroxybutyl (meth)acrylate; hydroxyethyl caprolactone (meth)acrylate; pentaerythritol tri(meth)acrylate; pentaerythritol tetra(meth)acrylate; dipentaerythritol penta(meth)acrylate; dipentaerythritol hexa(meth)acrylate; and combinations thereof.

[0116] Suitable polyester (meth)acrylate oligomers are obtained by reacting (meth)acrylic acid with a polyester prepared from a polyacid or its anhydride and a polyol. Examples of polyacids include, but are not limited to, phthalic acid; succinic acid; adipic acid; glutaric acid; sebacic acid; isosebacic acid; tetrahydrophthalic acid; hexahydrophthalic acid; dimer acid; trimellitic acid; pyromellitic acid; pimelic acid; and azelaic acid. Examples of polyols include, but are not limited to, 1,6-hexanediol; diethylene glycol; 1,2-propylene glycol; 1,3-butylene glycol; neopentyl glycol; dipropylene glycol; polyethylene glycol; and polypropylene glycol.

[0117] As known in the art, polyether (meth) acrylate oligomers can be obtained by transesterification between polyethers and (meth) acrylates (such as ethyl methacrylate). Exemplary polyethers include those obtained from ethoxylated or propoxylated trimethylolpropane, pentaerythritol, etc. or by polyetherification of 1,4-propylene glycol, etc.

[0118] In a preferred embodiment, the first part comprises at least one (meth)acrylate monomer selected from the group consisting of: methyl (meth)acrylate; ethyl (meth)acrylate; n-propyl (meth)acrylate; isopropyl (meth)acrylate; n-butyl (meth)acrylate; isobutyl (meth)acrylate; tert-butyl (meth)acrylate; n-pentyl (meth)acrylate; n-hexyl (meth)acrylate; cyclohexyl (meth)acrylate; n-heptyl (meth)acrylate; n-octyl (meth)acrylate; 2-ethylhexyl ... 2-hydroxyethyl (meth)acrylate; 2-hydroxypropyl (meth)acrylate; octadecyl (meth)acrylate; glycidyl (meth)acrylate; isobornyl (meth)acrylate; 2-aminoethyl (meth)acrylate; γ-(meth)acryloyloxy Propyltrimethoxysilane; (meth) acrylic acid-ethylene oxide adduct; trifluoromethyl methyl (meth) acrylate; 2-trifluoromethyl ethyl (meth) acrylate; 2-perfluoroethyl ethyl (meth) acrylate; 2-perfluoroethyl-2-perfluorobutylethyl (meth) acrylate; 2-perfluoroethyl (meth) acrylate; perfluoromethyl (meth) acrylate; diperfluoromethyl methyl (meth) acrylate; 2-perfluoromethyl-2-perfluoroethyl methyl (meth) acrylate; 2-perfluorohexylethyl (meth) acrylate; (meth) acrylate 2-Perfluorodecylethyl acrylate; 2-Perfluorohexadecylethyl (meth)acrylate; ethoxylated trimethylolpropane triacrylate; trimethylolpropane trimethacrylate; dipentaerythritol monohydroxypentaacrylate; pentaerythritol triacrylate; ethoxylated trimethylolpropane triacrylate; 1,6-hexanediol diacrylate; neopentyl glycol diacrylate; pentaerythritol tetraacrylate; 1,2-butanediol diacrylate; ethoxylated trimethylolpropane tri(meth)acrylate (trimethylopropane ethoxylate tri(meth)acrylate); glyceryl propoxylate tri(meth)acrylate; trimethylolpropane tri(meth)acrylate; dipentaerythritol monohydroxypenta(meth)acrylate; tripropylene glycol di(meth)acrylate; neopentylglycol propoxylate di(meth)acrylate; 1,4-butylene glycol di(meth)acrylate; triethylene glycol di(meth)acrylate; butanediol di(meth)acrylate; and ethoxylated bisphenol A di(meth)acrylate.

[0119] Good results have been obtained in the case where the first part comprises at least one (meth)acrylate monomer selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, isobornyl (meth)acrylate, ethoxylated trimethylolpropane triacrylate and trimethylolpropane triacrylate. Particular preference is given to using methyl methacrylate in the first part.

[0120] The (meth)acrylate monomers listed above are preferred because it is believed that the size of the monomers results in the formation of an ideal polymer network, which enhances ion transport.

[0121] It is known in the art that the introduction of certain additional non-polymeric functional groups into (meth)acrylate monomers can improve the surface adhesion of the polymer derived therefrom. In this regard, anhydride, phosphate or phosphonate functional groups may be mentioned, and (meth)acrylate monomers with such functional groups may be used in the first part of the composition of the invention. A list of such phosphorus compounds is found in U.S. Pat. No. 4,223,115. Exemplary monomers include: 2-monomethacryloxyethyl phosphate; bis(2-methacryloxyethyl) phosphate; 2-acryloxyethyl phosphate; bis-(2-acryloxyethyl) phosphate; (2-methacryloxyethyl) methyl phosphate; methacryloxyethyl ethyl phosphate; acryloxyethyl methyl phosphate; acryloxyethyl ethyl phosphate; 2-hydroxyethyl methacrylate phosphate; 10-[(2-methylprop-2eonyl)oxy]decyl dihydrogenphosphate (10-methacryloxydecyl dihydrogenphosphate); and 4-methacryloxyethyl trimellitic anhydride.

[0122] Copolymerizable acid

[0123] As indicated above, the first part of the composition comprises a copolymerizable acid, which should generally be employed in an amount of 0.5-20% by weight, based on the weight of the first part: the copolymerizable acid may preferably represent 5-15% by weight, for example 6-12% by weight of the first part. For the sake of completeness, although such monomers should generally be used in the form of free acids, it is not excluded that the constituent acid groups of the monomers are partially or completely neutralized by a suitable base, provided that this does not affect their participation in the copolymerization.

[0124] The copolymerizable acid is believed to improve the curing speed and metal adhesion of the composition. The aforementioned amount of the copolymerizable acid is preferred because an amount greater than 20 wt % based on the weight of the first part may cause corrosion problems and gas evolution, while an amount less than 0.5 wt % based on the weight of the first part may result in incomplete curing and thus reduce the initial adhesive properties.

[0125] Without intending to limit the invention, the copolymerizable acid monomer should be selected from: ethylenically unsaturated carboxylic acids; ethylenically unsaturated sulfonic acids; and vinylphosphonic acid. Suitable ethylenically unsaturated sulfonic acids are, for example, vinylsulfonic acid, styrenesulfonic acid and acrylamidomethylpropanesulfonic acid.

[0126] Preferably, the copolymerizable acid of the part comprises or consists of an ethylenically unsaturated carboxylic acid selected from: α,β-monoethylenically unsaturated monocarboxylic acid; α,β-monoethylenically unsaturated dicarboxylic acid; C 1 -C 6 Alkyl half esters; α,β-monoethylenically unsaturated tricarboxylic acids; and C α,β-monoethylenically unsaturated tricarboxylic acids having at least one free carboxylic acid group. 1 -C 6 In particular, the copolymerizable acid of the part comprises or consists of at least one acid selected from methacrylic acid, acrylic acid, itaconic acid, maleic acid, aconitic acid, crotonic acid and fumaric acid.

[0127] It is noted that the present invention does not exclude the presence of a vinyl monomer in the first part, which vinyl monomer can be copolymerized with the (meth)acrylate monomer and is selected from: styrene monomers such as styrene, vinyl toluene, α-methylstyrene and chlorostyrene; fluorine-containing vinyl monomers such as perfluoroethylene, perfluoropropylene and fluorinated vinylidene; silicon-containing vinyl monomers such as vinyl trimethoxysilane and vinyl triethoxysilane; maleimide monomers such as maleimide, methylmaleimide, ethylmaleimide, propylmaleimide, butylmaleimide, etc. amine, hexylmaleimide, octylmaleimide, dodecylmaleimide, octadecylmaleimide, phenylmaleimide and cyclohexylmaleimide; vinyl monomers containing nitrile groups, such as acrylonitrile and methacrylonitrile; vinyl monomers containing amide groups, such as acrylamide and methacrylamide; vinyl esters, such as vinyl acetate, vinyl propionate, vinyl pivalate, vinyl benzoate and vinyl cinnamate; olefins, such as ethylene and propylene; conjugated dienes, such as butadiene and isoprene; and vinyl chloride, vinylidene chloride, allyl chloride and allyl alcohol. However, when included, such vinyl comonomers should account for less than 40% by weight, preferably less than 20% by weight or less than 10% by weight based on the total weight of the copolymerizable acid monomers.

[0128] Electrolytes

[0129] The first part of the composition comprises 0.5-20 wt% electrolyte based on the weight of the first part: the electrolyte may preferably account for 5-15 wt%, for example 6-12 wt% of the first part. These amounts are preferred because an amount of electrolyte greater than 20 wt% based on the weight of the first part may produce a good debonding effect, but curing may be incomplete and thus may adversely affect the initial adhesive properties. Conversely, at an amount less than 0.5 wt% based on the weight of the first part, the debonding effect may be impaired.

[0130] The electrolyte comprises or consists of at least one salt according to formula (I) or formula (II):

[0131]

[0132] Where: R 1 , R 2 , R 3 , R 4 and R 5 are independently selected from hydrogen, C 1 -C 18 Alkyl, C 3 -C 18 Cycloalkyl, C 6 -C 18 Aryl,

[0133] C 7 -C 24 Aralkyl, C 2 -C 20 Alkenyl, -C(O)R q , -C(O)OH, -CN, or -NO 2 ; and R q It is C 1 -C 6

[0134] Alkyl; and

[0135] X - is a counter anion selected from the group consisting of:

[0136]

[0137] The general formula R a Japanese R b are independently selected from hydrogen, C 1 -C 12 Alkyl, C 5 -C 12 Cycloalkyl, C 5 -C 12 Heterocycloalkyl, C 6 -C 18Aryl, or C 5 -C 18 Heteroaryl.

[0138] For the sake of completeness, in formula (I) and formula (II), the term C 1 -C n Alkyl, C 3 -C n Cycloalkyl, C 6 -C 18 Aryl, C 7 -C 24 Aralkyl, C 2 -C 20 Alkenyl groups specifically include groups in which one or more hydrogen atoms are replaced by halogen atoms (e.g., C 1 -C 18 haloalkyl) or hydroxyl (e.g., C 1 -C 18 In particular, it is preferred that R 1 , R 2 , R 3 , R 4 and R 5 are independently selected from hydrogen, C 1 -C 18 Alkyl, C 1 -C 18 Haloalkyl, C 1 -C 18 Hydroxyalkyl, or C 3 -C 18 Cycloalkyl. For example, R 1 , R 2 , R 3 , R 4 and R 5 can be independently selected from hydrogen, C 1 -C 18 Alkyl, or C 1 -C 18 Halogenated alkyl.

[0139] Regarding the carboxylic acid imide, bis(sulfonyl)imide or sulfonyl imide counter anion (X) of formula (I) or formula (II): - ), preferably, R a and R b are independently selected from hydrogen, C 1 -C 12 Alkyl, or C 1 -C 12 For example, R a and R b can be independently selected from hydrogen, C 1 -C 8 Alkyl, or C1 -C 8 A haloalkyl group, or R a and R b can be independently selected from hydrogen, C 1 -C 4 Alkyl, or C 1 -C 4 A particularly preferred counter anion (X - ) is bis(trifluoromethylsulfonyl)imide.

[0140] The electrolyte of the first part is preferably selected from: 1-methylimidazolium bis(trifluoromethylsulfonyl)imide; 3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-butyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide; 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1- Octyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-methyl-3-octylimidazolium bis(trifluoromethylsulfonyl)imide; 1-decyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; tetraethylphosphonium bis(trifluoromethylsulfonyl)imide; tetrabutylphosphonium bis(trifluoromethylsulfonyl)imide; tridecyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide; trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl)amide; and mixtures thereof. There may be mentioned as particularly preferred use of at least one of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl)amide.

[0141] The presence of compatible electrolyte compounds that do not conform to formula (I) or formula (II) in the electrolyte is not excluded. However, the one or more compounds of formula (I) or formula (II) should account for at least 90% by weight of the electrolyte, preferably at least 95% by weight, more preferably at least 99% by weight, and most preferably 100% by weight.

[0142] Second part of a two-part (2K) composition

[0143] The second part of the two-part composition comprises: a first curing agent for the monomers of the first part; a second curing agent for the monomers of the first part; a wax; and a solubilizing agent.

[0144] First curing agent

[0145] As indicated above, the second part of the composition comprises a first curing agent which should generally be employed in an amount of 5-40 wt % based on the weight of the second part: the first curing agent may preferably constitute 10-40 wt %, such as 20-40 wt % of the second part.

[0146] These first curing agent amounts are preferred because amounts greater than 40 wt % based on the weight of the second part result in an excess of the first curing agent and undesired reactions that adversely affect the properties of the composition; whereas low amounts (mainly less than 5 wt %) result in incomplete curing and, therefore, poor initial adhesive properties.

[0147] In an important embodiment, the first curing agent comprises or consists of at least one free radical initiator, which decomposes under the action of heat to provide free radicals. Exemplary heat-activated free radical initiators include: peroxides, including ketone peroxides; hydroperoxides; peroxycarbonates; peracetic acid; azo compounds, such as 2,2'-azobisisobutyronitrile (AIBN) or 2,2'-azobis(2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanovaleric acid), or 1,1'-azobis(cyclohexanecarbonitrile); tetrazines; and persulfate compounds, such as potassium persulfate. Free radical initiators that are solid at room temperature are preferred. Independently or in addition to this preferred statement, it is desired that the free radical initiator has a half-life of at least 10 hours at a temperature of 60°C.

[0148] Although certain peroxides, such as dialkyl peroxides and diaryl peroxides, have been disclosed as useful curing agents, inter alia, in U.S. Pat. No. 3,419,512 (Lees) and U.S. Pat. No. 3,479,246 (Stapleton), and are in fact useful herein, hydroperoxides also represent an important class of curing agents for use in the present invention. In this context, although hydrogen peroxide itself may be used, organic hydroperoxides are preferably employed. For the sake of completeness, included within the definition of hydroperoxide are substances such as organic peroxides or organic peresters, which decompose or hydrolyze to form organic hydroperoxides in situ: examples of such peroxides and peresters are cyclohexyl peroxide and hydroxycyclohexyl peroxide, respectively, and t-butyl perbenzoate.

[0149] Without intending to limit the present invention, representative hydroperoxide compounds have the following general formula:

[0150] R p OOH

[0151] Where: R p is a hydrocarbon radical containing up to 18 carbon atoms, and

[0152] Preferably, Rp C 1 -C 12 Alkyl, C 6 -C 18 Aryl, or C 7 -C 18 Aralkyl.

[0153] As exemplary compounds that can be used as the first curing agent alone or in combination, there can be mentioned: cumene hydroperoxide (CHP); tert-butyl hydroperoxide (TBH); tert-butyl perbenzoate; tert-butyl peroxyacetate; tert-amyl hydroperoxide; 1,2,3,4-tetramethylbutyl hydroperoxide; lauryl peroxide; benzoyl peroxide (also known as dibenzoyl peroxide, C 14 H 10 O 4 , CAS No. 94-36-0); 1,3-bis(tert-butylperoxyisopropyl)benzene; diacetyl peroxide; butyl-4,4-bis(tert-butylperoxy)valerate; p-chlorobenzoyl peroxide; tert-butylcumyl peroxide; di-tert-butyl peroxide; diisopropylbenzene peroxide; 2,5-dimethyl-2,5-di-tert-butylperoxyhexane; 2,5-dimethyl-2,5-di-tert-butyl-peroxyhex-3-yne; and 4-methyl-2,2-di-tert-butylperoxypentane.

[0154] Preferably, the first curing agent is a peroxide or hydroperoxide compound selected from the following: tert-butyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, tert-butyl perbenzoate, diacetyl peroxide, benzoyl peroxide, tert-butyl peracetate, lauryl peroxide, and mixtures thereof; note that benzoyl peroxide is particularly preferred.

[0155] In the case where the first curing agent is an oxidizing agent (such as the aforementioned peroxide and hydroperoxide compounds), the composition may also include an activator. When combined in appropriate proportions, the oxidizing agent and the activating agent (reducing agent) generate polymerization initiating free radicals, even under mild conditions without a supplemental energy source. The oxidizing agent alone or both the oxidizing agent and the reducing agent can provide polymerization initiating free radicals.

[0156] Exemplary activators or reductants may be selected from: alkali metal sulfites; alkali metal bisulfites; alkali metal metabisulfites; formaldehyde sulfoxylates; alkali metal salts of aliphatic sulfinic acids; alkali metal hydrosulfides; metalhydrogensulfide); salts of polyvalent metals, in particular Co(II) salts and Fe(II) salts, such as iron(II) sulfate, ammonium iron(II) sulfate, or iron(II) phosphate; dihydroxymaleic acid; benzoin; ascorbic acid; reducing amines, in particular aromatic tertiary amines, such as N,N-bis(2-hydroxyethyl)-p-toluidine (diethanol-p-toluidine, DE-pT), 2-(4-dimethylaminophenyl)ethanol (DMAPE), 4-tert-butyldimethylaniline, 3-dimethylaminobenzoic acid, 4-dimethylaminobenzoic acid, ethyl 4-dimethylaminobenzoate (EDMAB), 2-ethylhexyl 4-dimethylaminobenzoate and 4-dimethylaminobenzoate; and reducing sugars, such as sorbose, glucose, fructose, and / or dihydroxyacetone.

[0157] It will be conventional for the activator (reducing agent) to be included in the first component together with the polymerizable species. However, it is not excluded that the activator is added to the second component immediately before the first component is contacted with the second component.

[0158] Second curing agent

[0159] As indicated above, the second part of the composition comprises a second curing agent which should generally be employed in an amount of 0.01-2 wt % based on the weight of the second part: the second curing agent may preferably constitute 0.01-1 wt %, such as 0.01-0.5 wt % of the second part.

[0160] In an important embodiment, the second curing agent comprises or consists of at least one compound, which is a salt or coordination compound of a transition metal, which can be selected from Fe, Co, V, Ti, Mn, Cu, Sn, Cr, Ni, Mo, Ge, Sr, Pd, Pt, Nb, Sb, Re, Os, Ir, Pt, Au, Hg, Te, Rb and Bi, and in particular should be selected from Fe, Co, V, Mn and Cu. Note that both Fe(II) coordination compounds and Fe(III) coordination compounds can be used.

[0161] It has been shown that the second reagent comprises at least one iron compound or is composed of at least one iron compound, which is advantageously selected from: iron carboxylate; 1,3-dioxo iron complex; ammonium ferrocyanide; and dicyclopentadienyl iron complex. In this regard, exemplary iron carboxylates include iron lactate, iron naphthenate, 2-ethylhexanoate iron (octoate iron), iron formate, iron acetate, iron propionate, butyrate, iron valerate, hexanoate, heptanoate, nonanoate, decanoate, neodecanoate, and dodecanoate. Exemplary 1,3-dioxo iron complexes include iron acetylacetonate, and iron complexes of acetylacetone, benzoylacetone, dibenzoylmethane, and acetoacetate (such as diethylacetoacetamide, dimethylacetoacetamide, dipropylacetoacetamide, dibutylacetoacetamide, methylacetoacetate, ethylacetoacetate, propylacetoacetate, and butylacetoacetate. Examples of dicyclopentadienyl iron coordination compounds are those comprising iron and two substituted or unsubstituted cyclopentadienyl ligands, wherein the optional substituents on the cyclopentadienyl ring are selected from C 1 -C 12 Alkyl, C 6 -C 18 Aryl and C 7 -C 18 Aralkyl. A specific example of the dicyclopentadienyl iron coordination compound is ferrocene (bis(η5-cyclopentadienyl)iron).

[0162] As other exemplary transition metal compounds that can be used in or as the second curing agent, salts and coordination compounds of copper, cobalt, vanadium and manganese can be particularly mentioned. In this article, cobalt compounds can be used as transition metals without legislative problems and toxicity problems (due to the small amount used). Suitable counter anions present in the salt include: halide; nitrate; sulfate; sulfonate; phosphate; phosphonate; oxide; or carboxylate, such as lactate, 2-ethylhexanoate, acetate, propionate, butyrate, oxalate, laurate, oleate, linoleate, palmitate, stearate, acetylacetonate, octanoate, nonanoate, heptanoate, neodecanoate or cyclohexaneate.

[0163] wax

[0164] Although the presence of wax in the first component is not excluded, the composition of the invention is characterized in that the second part comprises 5-30% by weight of at least one wax, based on the weight of the part. The one or more waxes may, for example, represent 5-20% by weight or 5-15% by weight of the second part. The at least one wax serves to limit the evaporation of the monomers present, in particular (meth)acrylate monomers, when mixing the first and second parts of the composition.

[0165] Without intending to limit the invention, the waxes useful in the present invention should have a softening point of 50-150°C and may include one or more of the following: polyethylene having a number average molecular weight (Mn) of 500-7500; petroleum waxes, such as paraffin wax and microcrystalline wax; synthetic waxes made by polymerizing carbon monoxide with hydrogen, such as Fischer-Tropsch wax; polyolefin waxes, including functionalized polyolefin waxes, of which maleated polyethylene, maleated polypropylene and maleated ethylene-propylene copolymers can be mentioned as examples; and hydrogenated animal, fish or vegetable oils.

[0166] Solubilizer

[0167] The second part of the two-part (2K) composition necessarily contains a solubilizer, which is conventionally present in an amount of 20-60 wt % based on the weight of the second part: preferably, the solubilizer comprises 30-60 wt %, such as 40-60 wt % of the second part. At amounts of solubilizer greater than 60 wt %, based on the weight of the second part, the adhesive and curing properties of the composition may be adversely affected.

[0168] The solubilizer has the function of promoting miscibility of the electrolyte within the adhesive composition formed after the two parts of the adhesive composition are mixed: the solubilizer may or may not form part of the polymer matrix (which is formed after the adhesive composition is cured), but does serve to promote ion transfer therein. Therefore, the solubilizer is preferably a polar compound and should desirably be liquid at room temperature.

[0169] In a first embodiment, the solubilizing agent comprises one or more liquid epoxy resins or is composed of one or more liquid epoxy resins. As used herein, epoxy resin can include monofunctional epoxy resin, multifunctional epoxy resin (multi-or poly-functional epoxy resins), and combinations thereof. Epoxy resin can be a pure compound, but can also be a mixture of epoxy-functional compounds, including a mixture of compounds with different numbers of epoxy groups per molecule. Epoxy resin can be saturated or unsaturated, aliphatic, alicyclic, aromatic or heterocyclic, and can be substituted. In addition, epoxy resin can be monomeric or polymeric.

[0170] Without intending to limit the present invention, exemplary monoepoxides include: alkylene oxides; epoxy-substituted alicyclic hydrocarbons, such as cyclohexene oxide, vinylcyclohexene monooxide, (+)-cis-limonene oxide, (+)-cis,trans-limonene oxide, (-)-cis,trans-limonene oxide, cyclooctene oxide, cyclododecene oxide, and α-pinene oxide; epoxy-substituted aromatic hydrocarbons; monoepoxy-substituted alkyl ethers of monohydric alcohols or phenols, such as glycidyls of aliphatic, alicyclic and aromatic alcohols; ethers; monoepoxy-substituted alkyl esters of monocarboxylic acids, such as glycidyl esters of aliphatic, cycloaliphatic and aromatic monocarboxylic acids; monoepoxy-substituted alkyl esters of polycarboxylic acids, in which one or more other carboxyl groups are esterified with alkanols; alkyl and alkenyl esters of epoxy-substituted monocarboxylic acids; epoxy alkyl ethers of polyols, in which one or more other OH groups are esterified or etherified with carboxylic acids or alcohols; and monoesters of polyols and epoxy monocarboxylic acids, in which one or more other OH groups are esterified or etherified with carboxylic acids or alcohols.

[0171] For example, the following glycidyl ethers can be mentioned as monoepoxy compounds suitable for use herein: methyl glycidyl ether; ethyl glycidyl ether; propyl glycidyl ether; butyl glycidyl ether; pentyl glycidyl ether; hexyl glycidyl ether; cyclohexyl glycidyl ether; octyl glycidyl ether; 2-ethylhexyl glycidyl ether; allyl glycidyl ether; benzyl glycidyl ether; phenyl glycidyl ether; 4-tert-butylphenyl glycidyl ether; 1-naphthyl glycidyl ether; 2-naphthyl glycidyl ether; 2-chlorophenyl glycidyl ether; 4-chlorophenyl glycidyl ether; 4-bromophenyl glycidyl ether; 2,4,6-trichlorophenyl glycidyl ether; 2,4,6-tribromophenyl glycidyl ether; pentafluorophenyl glycidyl ether; o-cresyl glycidyl ether; m-cresyl glycidyl ether; and p-cresyl glycidyl ether.

[0172] In certain embodiments, the monoepoxide conforms to Formula (III) below:

[0173]

[0174] Where: R w , R x , R y and R z may be the same or different and are independently selected from hydrogen, halogen atoms, C 1 -C 8 Alkyl, C 3 -C 10 Cycloalkyl, C 2 -C 12 Alkenyl, C 6 -C 18 Aryl, or C 7 -C 18 Arylalkyl, provided that Ry and R z At least one of is not hydrogen.

[0175] Preferably, R w , R x and R y is hydrogen, and R z Phenyl or C 1 -C 8 Alkyl, more preferably C 1 -C 4 alkyl.

[0176] In view of these embodiments, exemplary monoepoxides include: ethylene oxide; 1,2-propylene oxide (propylene oxide); 1,2-butylene oxide; cis-2,3-butylene oxide; trans-2,3-butylene oxide; 1,2-pentene oxide; 1,2-hexene oxide; 1,2-heptane oxide; decane oxide; butadiene oxide; isoprene oxide; and styrene oxide.

[0177] In the present invention, it is mentioned to use at least one monoepoxide compound selected from the group consisting of ethylene oxide; propylene oxide; cyclohexene oxide; (+)-cis-limonene oxide; (+)-cis,trans-limonene oxide; (-)-cis,trans-limonene oxide; cyclooctene oxide; and cyclododecene oxide.

[0178] Again, without intending to limit the invention, suitable polyepoxides may be liquids, solids, or solutions in solvents. Additionally, such polyepoxides should have an epoxy equivalent weight of 100 to 700 g / equivalent, such as 120 to 320 g / equivalent. Additionally, typically, diepoxides having an epoxy equivalent weight of less than 500 g / equivalent or even less than 400 g / equivalent are preferred: this is primarily from a cost perspective, since lower molecular weight epoxy resins require more limited processing in purification in their production.

[0179] As examples of types or groups of polyepoxides that can be polymerized in the present invention, mention may be made of: glycidyl ethers of polyols and polyphenols; glycidyl esters of polycarboxylic acids; and epoxidized polyethylenically unsaturated hydrocarbons, esters, ethers and amides.

[0180] Suitable diglycidyl ether compounds may be aromatic, aliphatic or cycloaliphatic in nature and may thus be derived from dihydric phenols and diols. In addition, useful classes of such diglycidyl ethers are: diglycidyl ethers of aliphatic and cycloaliphatic diols such as 1,2-ethanediol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,12-dodecanediol, cyclopentanediol and cyclohexanediol; diglycidyl ethers based on bisphenol A; bisphenol F diglycidyl ethers; diglycidyl ethers based on polyalkylene glycols, in particular polypropylene glycol diglycidyl ethers; and glycidyl ethers based on polycarbonate diols.

[0181] Additional illustrative polyepoxides include, but are not limited to: glycerol polyglycidyl ether; trimethylolpropane polyglycidyl ether; pentaerythritol polyglycidyl ether; diglycerol polyglycidyl ether; polyglycerol polyglycidyl ether; and sorbitol polyglycidyl ether.

[0182] The glycidyl esters of polycarboxylic acids useful in the present invention are derived from polycarboxylic acids containing at least two carboxylic acid groups and containing no other groups reactive to epoxy groups. The polycarboxylic acids may be aliphatic, alicyclic, aromatic and heterocyclic. Preferred polycarboxylic acids are those containing no more than 18 carbon atoms per carboxylic acid group, suitable examples of which include, but are not limited to: oxalic acid; sebacic acid; adipic acid; succinic acid; pimelic acid; suberic acid; glutaric acid; dimer and trimer acids of unsaturated fatty acids, such as dimer and trimer acids of linseed fatty acids; phthalic acid; isophthalic acid; terephthalic acid; trimellitic acid; trimesic acid; phenylacetic acid; chlorendic acid; hexahydrophthalic acid, in particular hexahydrophthalic acid (1,2-cyclohexanedicarboxylic acid); biphenyl dicarboxylic acid; naphthalene dicarboxylic acid; esters of polyacid-terminated esters of dibasic acids and aliphatic polyols; polymers and copolymers of (meth) acrylic acid; and crotonic acid.

[0183] Other suitable diepoxides that may also be mentioned include: diunsaturated fatty acids C 1 -C 18 Alkyl ester diepoxides; butadiene diepoxides; polybutadiene diglycidyl ether; vinyl cyclohexene diepoxides; and limonene diepoxides.

[0184] In addition, preferred examples of polyepoxides include: bisphenol A epoxy resins, such as DER TM 331、DER TM 332、DER TM 383、JER TM 828 and Epotec YD 128; bisphenol F epoxy resins, such as DER TM 354; Bisphenol A / F epoxy resin blends, such as DER TM353; Aliphatic glycidyl ethers, such as DER TM 736; Polypropylene glycol diglycidyl ether, such as DER TM 732; Epoxy novolac resin, such as DEN TM 438; Brominated epoxy resins, such as DER TM 542; Castor oil triglycidyl ether, such as ERISYS TM GE-35H; Polyglycerol-3-polyglycidyl ether, such as ERISYS TM GE-38; Sorbitol glycidyl ether, such as ERISYS TM GE-60; and bis(2,3-epoxypropyl)cyclohexane-1,2-dicarboxylate available as Lapox Arch-11. Note that a solubilizing agent comprising or consisting of a bisphenol A epoxy resin is particularly preferred.

[0185] In the case where the solubilizing agent of the second part of the composition is based on one or more epoxy resins, the present invention does not exclude that the solubilizing agent also contains one or more cyclic compounds selected from the group consisting of: oxetanes; cyclic carbonates; cyclic anhydrides; and lactones. The disclosure of the following citations may be instructive in disclosing suitable cyclic carbonate functional compounds: U.S. Patent No. 3,535,342; U.S. Patent No. 4,835,289; U.S. Patent No. 4,892,954; British Patent No. GB-A-1,485,925; and EP-A-0 119 840. However, based on the total weight of the epoxy compound, such additional cyclic compounds should account for less than 20% by weight, preferably less than 10% by weight or less than 5% by weight.

[0186] In another embodiment, which is not intended to be mutually exclusive with the embodiments given above, the solubilizing agent of the second part comprises at least one polymer which is liquid at room temperature and is selected from: polyphosphazene; polymethylene sulfide; polyoxyalkylene glycol; and polyethylene imine. It can be noted that preferably the polyoxyalkylene glycol has a weight average molecular weight of 350 to 10000 g / mol, for example 500 to 5000 g / mol. 2 -C 3 )Alkylene glycol.

[0187] Toughening agent

[0188] The composition of the present invention comprises a toughening agent, which may be present in either or both of the first part (A) and the second part (B) of the composition. However, it is preferred that the first component (A) comprises a toughening agent. In addition, the presence of a toughening agent in the composition facilitates the debonding of the cured adhesive. Without intending to be bound by theory, the toughening agent promotes phase separation within the cured adhesive under the application of an electric potential.

[0189] Preferably, the toughening agent should be included in the composition in an amount of 5-40 wt %, for example 10-40 wt % or 20-40 wt %, based on the total weight of the composition. These toughening agent amounts are preferred because amounts greater than 40 wt % result in insufficient adhesive properties, while amounts less than 5 wt % result in insufficient debonding effects and overly flexible compositions.

[0190] Good results have been obtained in the case where the composition of the invention comprises at least one toughening agent selected from: a non-reactive elastomer; and core-shell rubber particles. The presence of a non-reactive elastomer in the composition is preferred. It may be noted that it is particularly preferred to include a toughening agent in the first part of the composition, the toughening agent comprising or consisting of at least one non-reactive elastomer.

[0191] The term "non-reactive" as applied to the elastomeric component of the composition of the present invention means that the polymer does not contain activated double bonds capable of free radical polymerization. The term "elastomeric" is defined as having the ability of a polymer to recover to its approximate original length after being elongated below its rupture or breaking point when provided as a strip.

[0192] Exemplary non-reactive elastomers useful in the present invention include, but are not limited to: i) elastomeric homopolymers of dienes, such as 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2-chloro-1,3-butadiene (chloroprene), 2,3-dimethyl-1,3-butadiene, 1,4-dimethyl-1,3-butadiene, 1,3-pentylene, 1,3-hexadiene, 2-methyl-1,3-pentadiene, 2-methyl-3-butyl-1,3-butadiene, and 2,3-diethyl-1,3-butadiene; ii) homopolymers of dienes with at least one modifying ethylenically unsaturated comonomer, such as ethylene, propylene, isobutylene, styrene, α-(C 1 -C 4 -alkyl)styrene, (meth)acrylonitrile and methyl methacrylate), wherein the one or more comonomers may typically constitute 5-40 wt. % of the copolymer; iii) (meth)acrylic elastomeric polymers, such as all acrylic-based thermoplastic elastomers (TPE); iv) natural rubber; and v) polyethylene, polypropylene and ethylene-propylene copolymers.

[0193] As exemplary non-reactive elastomers, mention may be made of: ethylene / propylene / diene terpolymers; (meth)acrylonitrile-butadiene copolymers; (meth)acrylonitrile-styrene copolymers; (meth)acrylonitrile-butadiene-styrene copolymers; styrene-isoprene-styrene copolymers; styrene-butadiene-styrene copolymers; and ABA triblock copolymers, wherein block A and block B are composed of (meth)acrylic acid C having different glass transition temperatures (Tg), respectively. 1 -C 8 Alkyl esters, such as PMMA-PnBA-PMMA and PMMA-P(nBA / 2-EHA)-PMMA triblock copolymers based on methyl (meth)acrylate (MMA), n-butyl acrylate (nBA) and 2-ethylhexyl acrylate (2-EHA). Commercial examples include: Available from Enichem Elastomers Americas, Inc; Hypro 200X 168LC VTB, available from Huntsman; Kraton D1155 ES, available from Kraton Corporation; Kurarity LA4285 (PMMA-PnBA-PMMA triblock copolymer), available from Kuraray Co. Ltd.; Blendex 338, available from Galata Chemicals; and Nipol 1472X, available from Zeon Chemicals.

[0194] As noted, the composition may optionally include a toughening rubber in the form of core-shell particles dispersed in a polymer matrix. The term "core-shell rubber" or CSR is used according to its standard meaning in the art to represent a rubber particle core and a shell layer, wherein the rubber particle core is formed by a polymer comprising an elastomer or rubbery polymer as a primary component and the shell layer is formed by a polymer grafted onto the core. The shell layer partially or completely covers the surface of the rubber particle core during the graft polymerization process. By weight, the core should account for at least 50% by weight of the core-shell rubber particles.

[0195] The polymer material of the core should have a glass transition temperature (T g ), preferably a glass transition temperature (T ) of -20°C or lower, more preferably -40°C or lower, even more preferably -60°C or lower g The polymer of the shell has a glass transition temperature (T g ) is a non-elastomeric, thermoplastic or thermosetting polymer having a temperature greater than room temperature, preferably greater than 30°C, more preferably greater than 50°C.

[0196] Without intending to limit the invention, the core may comprise: a diene homopolymer, such as a homopolymer of 1,3-butadiene or 2-methyl-1,3-butadiene (isoprene); a diene copolymer, such as a copolymer of 1,3-butadiene or isoprene with one or more ethylenically unsaturated monomers such as vinyl aromatic monomers, (meth)acrylonitrile, or (meth)acrylates; a polymer based on (meth)acrylate monomers such as polybutyl acrylate; and a polysiloxane elastomer such as polydimethylsiloxane and cross-linked polydimethylsiloxane.

[0197] Similarly, without limiting the invention, the shell may comprise a polymer or copolymer of one or more monomers selected from: (meth)acrylates, such as methyl methacrylate; vinyl aromatic monomers, such as styrene; vinyl cyanides, such as acrylonitrile; unsaturated acids and anhydrides, such as acrylic acid; and (meth)acrylamide. The polymer or copolymer used in the shell may have acid groups that are ionically crosslinked by metal carboxylate formation, in particular by forming salts of divalent metal cations. The shell polymer or copolymer may also be covalently crosslinked by monomers having two or more double bonds per molecule.

[0198] Preferably, any included core-shell rubber particles have an average particle size (d50) of 10 nm to 300 nm, for example 50 nm to 250 nm: the particle size refers to the diameter or maximum dimension of the particle in the particle distribution and is measured via dynamic light scattering. For the sake of completeness, the present application does not exclude the presence of two or more types of core-shell rubber (CSR) particles having different particle size distributions in the composition to provide a balance of key properties of the resulting cured product, including shear strength, peel strength and resin fracture toughness.

[0199] The core-shell rubber may be selected from commercially available products, examples of which include: Paraloid EXL 2650A, EXL2655 and EXL2691A, available from The Dow Chemical Company; XT100, available from Arkema Inc.; Kane The MX series, in particular MX 120, MX 125, MX 130, MX 136, MX 551, MX 553, are available from Kaneka Corporation; and METABLEN SX-006, is available from Mitsubishi Rayon.

[0200] Rheology Control Agents

[0201] The two-part (2K) composition of the present invention is characterized by the presence of a rheology control agent. Such an agent may be contained in the first part (A) or the second part (B) of the composition or in both parts of the composition. When a rheology control agent is provided in both parts of the composition, the characteristics of the agent in each part are determined independently and may therefore be the same or different for each part. Preferably, the first part (A) of the composition contains a rheology control agent.

[0202] The rheology control agent may consist of: a non-conductive filler; a conductive filler; or a mixture thereof.

[0203] The presence of non-conductive fillers in the composition can be used to adjust the viscosity of the composition and reduce the thermal expansion coefficient of the adhesive. In general, it is not intended to particularly limit the shape of the particles used as non-conductive fillers: needle-shaped, spherical, ellipsoidal, cylindrical, beaded, cubic or flaky particles can be used alone or in combination. In addition, it is envisioned that agglomerates of more than one particle type can be used. Likewise, it is not intended to particularly limit the size of the particles used as non-conductive fillers. However, such non-conductive fillers will conventionally have an average volume particle size of 0.01-1500 μm, such as 0.1-1000 μm or 0.1-500 μm as measured by laser diffraction / scattering methods.

[0204] Exemplary non-conductive fillers include, but are not limited to, chalk, lime powder, precipitated silica, fumed silica, zeolite, bentonite, magnesium carbonate, diatomaceous earth, alumina, clay, talc, sand, quartz, flint, mica, glass powder, zinc oxide and other ground minerals. Short fibers such as glass fibers, glass filaments, polyacrylonitrile, carbon fibers, polyethylene fibers may also be added.

[0205] It is preferred to use precipitated silica and / or fumed silica as a rheology control agent in the composition of the present invention: such precipitated silica or fumed silica should desirably have a viscosity of 25-500 m 2 / g, for example 100-250m 2 / g of BET surface area as measured by means of nitrogen adsorption in accordance with DIN 66131. ​​A commercial example of such a fumed (fumed) silica is Aerosil 200, available from Evonik Industries.

[0206] Also suitable as non-conductive fillers are hollow spheres with a mineral shell or a plastic shell. These are available, for example, under the trade name Glass Commercially available hollow glass spheres. Plastic-based hollow spheres (such as or ) can be used and are described in EP 0 520 426 B1: they are made of inorganic or organic substances and each have a diameter of 1 mm or less, preferably 500 μm or less, preferably 100 μm to 200 μm.

[0207] Non-conductive fillers which impart thixotropy to the composition may be useful in certain applications: such fillers are also described as rheology modifiers, for example hydrogenated castor oil, fatty acid amides, or expandable plastics such as PVC.

[0208] As indicated, the composition according to the invention may additionally comprise a conductive filler as at least part of the rheology control agent. In general, it is not intended to particularly limit the shape of the particles used as conductive fillers: needle-shaped, spherical, ellipsoidal, cylindrical, bead-shaped, cubic or plate-shaped particles may be used alone or in combination. In addition, it is envisaged that agglomerates of more than one particle type may be used. Likewise, it is not intended to particularly limit the size of the particles used as conductive fillers. However, such conductive fillers will conventionally have an average volume particle size as measured by laser diffraction / scattering methods of 1-500 μm, for example 1-200 μm.

[0209] Exemplary conductive fillers include, but are not limited to, silver; copper; gold; palladium; platinum; nickel; gold-plated nickel or silver-plated nickel; carbon black; carbon fiber; graphite; aluminum; indium tin oxide; silver-plated copper; silver-plated aluminum; metal-plated glass spheres; metal-plated fillers; metal-plated polymers; silver-plated fibers; silver-plated spheres; antimony-doped tin oxide; conductive nanospheres; nanosilver; nanoaluminum; nanocopper; nanonickel; carbon nanotubes; carbon nanostructures; and mixtures thereof. Preferably, particulate silver and / or carbon black and / or carbon nanostructures are used as conductive fillers.

[0210] The total amount of rheology control agent present in the composition of the present invention will preferably be 1-20 wt%, more preferably 1-10 wt%, based on the total weight of the composition. The desired viscosity of each part of the two-part (2K) composition and the desired viscosity of the curable composition formed when the parts are mixed will generally determine the total amount of rheology control agent added. The viscosity of each part of the two-part composition should desirably be 3000 to 150000, for example 5000 to 100000: within such a viscosity range, each part should be easily extruded from a suitable dispensing device (such as a tube).

[0211] Deoxidizer

[0212] The two-part (2K) composition of the present invention is characterized by the presence of at least one oxygen scavenger. The composition may comprise 0.1-5 wt% of the oxygen scavenger, based on the weight of the composition. Preferably, the composition comprises 0.1-2 wt%, such as 0.1-1 wt% of the oxygen scavenger.

[0213] The one or more oxygen scavengers may be included in the first part (A) or the second part (B) of the composition or in both parts of the composition. When oxygen scavengers are provided in both parts of the composition, the characteristics of the oxygen scavengers in each part are determined independently and may therefore be the same or different for each part. It is preferred herein that the first part of the composition comprises an oxygen scavenger.

[0214] The oxygen scavenger is reactive toward active oxygen species and should also be stable when in contact with oxygen or air at room temperature. Examples of suitable oxygen scavengers include: alkylated phenols; alkylated bisphenols; alkylene bisphenols, alkylene triphenols, and alkylene polyphenols; thio-, bis-, tri-, and polyalkylated phenols; sulfur-containing esters; organic phosphines; organic phosphites; organic phosphates; hydroquinones; inorganic compounds such as sulfates, sulfites, phosphites, and nitrites of metals, particularly those of Groups 1 and 2 of the Periodic Table and the first row of transition metals, zinc, and tin; sulfur-containing compounds such as thiodipropionic acid and its esters and salts, and thiobis(ethylene glycol β-aminocrotonate); amino acids such as cysteine ​​and methionine; and nitrogen-containing compounds capable of reacting with active oxygen species, including primary, secondary, and tertiary amines. Preferably, the oxygen scavenger is selected from: triphenylphosphine; triethyl phosphite; triisopropyl phosphite; triphenyl phosphite; tris(nonylphenyl) phosphite; butylated hydroxytoluene; butylated hydroxyanisole; tris(2,4-di-tert-butylphenyl) phosphite; dilauryl thiodipropionate; 2,2-methylene-bis-(6-tert-butyl-p-cresol); tetrakis(2,4-di-tert-butylphenyl) 4,4'-biphenylene diphosphonate; poly(4-vinylpyridine); and mixtures thereof.

[0215] It should be noted that the oxygen scavenger may be in polymeric or oligomeric form. Such forms may be prepared by covalently bonding a compound (such as those oxygen scavengers listed) to a monomer or comonomer. The limitation on the molecular size of the oxygen scavenger is its effect, if any, on the functional properties of any other polymer with which it is combined.

[0216] Additives and auxiliary ingredients

[0217] The compositions obtained in the present invention will generally also contain adjuvants and additives that can impart improved properties to these compositions. For example, adjuvants and additives can impart one or more of the following: improved elasticity; improved elastic recovery; longer permissible processing time; faster curing time; and lower residual viscosity. Such adjuvants and additives that can be included in a single part or both parts of a two-part (2K) composition independently of one another include: activators; plasticizers; stabilizers, including UV stabilizers; reactive diluents; non-reactive diluents; desiccants; adhesion promoters; bactericides; flame retardants; dyes; and colored pigments or pastes.

[0218] Such adjuvants and additives can be used in such combinations and proportions as desired, provided that they do not adversely affect the characteristics and basic properties of the composition. Although there are exceptions in some cases, these adjuvants and additives should not account for more than 50% by weight of the total composition, and preferably should not account for more than 20% by weight of the composition.

[0219] For the sake of completeness, it should be noted that adjuvant materials and additives containing reactive groups are generally blended into the appropriate parts of a two-part (2K) composition to ensure its storage stability. Non-reactive materials may be formulated into either or both parts.

[0220] A "plasticizer" for the purposes of the present invention is a substance that reduces the viscosity of the composition and thereby promotes its processability. In this context, the plasticizer may represent up to 10% by weight or up to 5% by weight, based on the total weight of the composition, and is preferably selected from: polydimethylsiloxane (PDMS); diurethane; monofunctional, linear or branched C 4 -C 16 Ethers of alcohols, such as Cetiol OE (available from Cognis Deutschland GmbH, Düsseldorf); rosin esters, butyrates, thiobutyrates, acetates, propionates and citrates; esters based on nitrocellulose and polyvinyl acetate; fatty acid esters; dicarboxylates; esters of fatty acids with OH groups or epoxidized; glycolates; benzoates; phosphates; sulfonates; trimellitates; epoxidized plasticizers; polyether plasticizers, such as end-capped polyethylene glycols or polypropylene glycols; polystyrene; hydrocarbon plasticizers; chlorinated paraffins; and mixtures thereof. It should be noted that, in principle, phthalates can be used as plasticizers, but these are not preferred due to their toxicological potential. Preferably, the plasticizer comprises or consists of one or more polydimethylsiloxanes (PDMS).

[0221] "Stabilizer" for the purposes of the present invention is understood to be an antioxidant, a UV stabilizer or a hydrolysis stabilizer. In this context, the stabilizer may constitute up to 10% by weight or up to 5% by weight, based on the total weight of the composition. Standard commercial examples of stabilizers suitable for use herein include: sterically hindered phenols; thioethers; benzotriazoles; benzophenones; benzoates; cyanoacrylates; acrylates; hindered amine light stabilizer (HALS) type amines; phosphorus; sulfur; and mixtures thereof.

[0222] In order to even further increase the shelf life, it is generally recommended to further stabilize the composition of the invention with respect to moisture penetration by using a desiccant. It is sometimes also necessary to reduce the viscosity of the adhesive composition of the invention for a particular application by using one or more reactive diluents. The total amount of reactive diluent present will typically be 0-15 wt %, e.g. 0-5 wt %, based on the total weight of the composition.

[0223] In certain embodiments, it may be meaningful to include a dye in a two-part (2K) composition. Desirably, the first part of the composition should include the added dye. It is believed that one skilled in the art will be able to select an appropriate dye based, inter alia, on the desired color of the cured adhesive as well as lightfastness, cost, toxicological properties, and solubility of the dye in the carrier medium. Typically, suitable dyes will be selected from the classes of azo, anthraquinone, and triphenylmethane type dyes, and the dye may be chemically modified to increase its solubility in the carrier medium or to reduce its adsorption to the substrate surface to which the adhesive is applied. Exemplary dyes that may be mentioned include PV Fast Blue BG and PV Fast Red B, available from Clariant KK.

[0224] The presence of solvents and non-reactive diluents in the compositions of the invention is not excluded insofar as they can usefully adjust the viscosity of the composition. For example, but by way of illustration only, the composition may include one or more of the following: xylene; 2-methoxyethanol; dimethoxyethanol; 2-ethoxyethanol; 2-propoxyethanol; 2-isopropoxyethanol; 2-butoxyethanol; 2-phenoxyethanol; 2-benzyloxyethanol; benzyl alcohol; ethylene glycol; ethylene glycol dimethyl ether; ethylene glycol diethyl ether; ethylene glycol dibutyl ether; ethylene glycol diphenyl ether; diethylene glycol; diethylene glycol monomethyl ether; diethylene glycol monoethyl ether; diethylene glycol mono-n-butyl ether; diethylene glycol dimethyl ether; diethylene glycol diethyl ether; diethylene glycol di-n-butyl ether; propylene glycol butyl ether; propylene glycol phenyl ether; dipropylene glycol; dipropylene glycol monomethyl ether; dipropylene glycol dimethyl ether; dipropylene glycol di-n-butyl ether; N-methylpyrrolidone; diphenylmethane; diisopropylnaphthalene; petroleum fractions, such as products (available from Exxon); alkylphenols, such as tert-butylphenol, nonylphenol, dodecylphenol and 8,11,14-pentadecatrienylphenol; styrenated phenols; bisphenols; aromatic hydrocarbon resins, especially those containing phenolic groups, such as ethoxylated or propoxylated phenols; adipates; sebacates; phthalates; benzoates; organic phosphates or sulfonates; and sulfonamides.

[0225] In addition to the above, it is preferred that the non-reactive diluents account for less than 10 wt %, in particular less than 5 wt % or less than 2 wt %, based on the total weight of the composition.

[0226] Illustrative Embodiments of Two-Part (2K) Compositions

[0227] In an exemplary embodiment of the present invention, a two-part (2K) adhesive composition comprises:

[0228] A first part (A), based on the weight of the first part, the first part (A) comprises:

[0229] 30-60 wt %, preferably 35-50 wt % of (meth)acrylate monomers, wherein the (meth)acrylate monomers comprise at least one C of (meth)acrylic acid. 1 -C 6 Alkyl esters;

[0230] 5-15 wt%, preferably 6-12 wt% of a copolymerizable acid, wherein the copolymerizable acid is selected from methacrylic acid, acrylic acid, itaconic acid, maleic acid, aconitic acid, crotonic acid, fumaric acid, and mixtures thereof; and

[0231] 5-15 wt %, preferably 6-12 wt % of an electrolyte, wherein the electrolyte is selected from 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, and mixtures thereof; and

[0232] A second part (B), based on the weight of the second part, the second part (B) comprises:

[0233] 10-40% by weight, preferably 20-40% by weight, of a first curing agent, which comprises or consists of at least one free radical initiator which decomposes under the action of heat to provide free radicals;

[0234] 0.01-1 wt%, preferably 0.01-0.5 wt% of a second curing agent, the second curing agent consisting of at least one compound, the at least one compound being a salt or coordination compound of a transition metal selected from Fe, Co, V, Mn and Cu; 5-20 wt%, preferably 5-15 wt% of a wax; and

[0235] 30-60 wt. %, preferably 40-60 wt. % of a solubilizer,

[0236] Wherein, based on the total weight of the composition, the first part (A) of the two-part (2K) adhesive composition further comprises:

[0237] 10-40 wt%, preferably 20-40 wt% of a toughening agent selected from the group consisting of non-reactive elastomers, core-shell rubber particles, and mixtures thereof;

[0238] 0.1-2 wt%, preferably 0.1-1 wt% of an oxygen scavenger; and

[0239] 1-10% by weight of a rheology control agent,

[0240] Further wherein the first part (A) and the second part (B) are mixed in an A:B weight ratio of 15:1 to 5:1, preferably 12:1 to 8:1, most preferably 10:1.

[0241] In this embodiment, it is preferred that the first curing agent is a peroxide or hydroperoxide compound selected from the group consisting of tert-butyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, tert-butyl perbenzoate, diacetyl peroxide, benzoyl peroxide, tert-butyl peracetate, lauryl peroxide, and mixtures thereof; note that benzoyl peroxide is particularly preferred. Independently or additionally to this preferred statement about the first curing agent, the second curing agent preferably comprises or consists of at least one iron-based compound selected from ferrocene, iron (II) acetylacetonate and hexa(cyano-C)ferrate (4-) iron (3+) ammonium.

[0242] It is also preferred in this embodiment that the toughening agent comprises or consists of at least one non-reactive elastomer.

[0243] Methods and Applications

[0244] To form the defined two-part (2K) curable composition, the reactive parts are combined together and mixed in such a way as to cause them to harden. The reactive compounds should be mixed under sufficient shear to produce a homogenous mixture that is preferably free of bubbles (foam) when mixed. It is believed that this can be achieved without the need for special conditions or special equipment. That is, suitable mixing devices may include: static mixing devices; magnetic stir bar devices; whipping devices; auger; batch mixer; planetary mixer; CW Brabender or mixers; and high shear mixers, such as blade blenders and rotary mixers.

[0245] For small-scale applications, in which volumes of less than 2 litres will generally be used, the preferred packaging for the two-part (2K) composition will be a side-by-side double cartridge or coaxial cartridge, in which two tubular chambers (generally of equal volume) are arranged side by side or nested in one another and sealed with pistons: the actuation of these pistons allows the parts to be extruded from the cartridges, advantageously by means of a static or dynamic mixer mounted in close proximity. For applications of larger volumes, the two parts of the composition may advantageously be stored in drums or barrels: in this case, the two parts are extruded via a hydraulic press, in particular by means of a follower plate, and supplied via a pipe to a mixing device which can ensure a fine and highly uniform mixing of the two parts. In any case, for any packaging, it is important that the parts are provided with airtight and watertight seals so that the two parts can be stored for a long time (ideally, 12 months or more).

[0246] Non-limiting examples of two-part dispensing apparatus and methods that may be suitable for use with the present invention include those described in US Pat. No. 6,129,244 and US Pat. No. 8,313,006.

[0247] Depending on the desired properties of the cured composition, the two parts will conventionally be mixed in a Part A:Part B weight ratio of 20:1 to 1:1, e.g., 15:1 to 5:1 or 12:1 to 8:1. A particularly preferred embodiment of the composition has a Part A:Part B weight ratio of 10:1.

[0248] According to the broadest method aspect of the present invention, the above-mentioned composition is applied to one or more material layers and then cured in situ. Before applying the composition, it is generally recommended to pretreat the relevant surface to remove foreign matter therefrom: if applicable, this step can promote the subsequent adhesion of the composition thereto. Such treatments are known in the art and can be carried out in a single-stage or multi-stage manner consisting of, for example, one or more of the following: etching treatment with an acid suitable for the substrate and an optional oxidant; ultrasonic treatment; plasma treatment, including chemical plasma treatment, corona treatment, atmospheric pressure plasma treatment and flame plasma treatment; immersion in an aqueous alkaline degreasing bath; treatment with an aqueous cleaning emulsion; treatment with a cleaning solvent (such as carbon tetrachloride or trichloroethylene); and water rinsing, preferably with deionized water or demineralized water. In those cases where an aqueous alkaline degreasing bath is used, any degreasing agent remaining on the surface should be removed by rinsing the substrate surface with deionized water or demineralized water.

[0249] The composition is then applied to the preferably pretreated surface of the substrate by conventional application methods such as: brushing; roller coating, knife application; printing methods; and spraying methods, including but not limited to air atomized spraying, air-assisted spraying, airless spraying and high volume low pressure spraying.

[0250] As indicated above, the present invention provides a bonded structure comprising: a first material layer having a conductive surface; and a second material layer having a conductive surface, wherein a cured debondable two-part (2K) adhesive composition as defined above and in the appended claims is disposed between the first material layer and the second material layer. To produce such a structure, the adhesive composition may be applied to at least one inner surface of the first material layer and / or the second material layer, and then the two layers are subsequently contacted so that the curable and debondable adhesive composition according to the present invention is disposed between the two layers.

[0251] It is recommended that the composition be applied to the surface at a wet film thickness of 10-500 μm. Application of thinner layers within this range is more economical and provides a reduced likelihood of deleterious thick cured areas. However, strict control must be exercised when applying thinner coatings or layers to avoid the formation of discontinuous cured films.

[0252] Curing of the applied composition of the invention typically occurs at a temperature in the range of 20°C to 200°C, preferably 25°C to 100°C, for example 25°C to 80°C or 25°C to 65°C. Suitable temperatures depend on the specific compounds present and the desired cure rate and can be determined in each case by a person skilled in the art using simple preliminary tests (if necessary). Of course, curing at lower temperatures in the aforementioned range is advantageous because it eliminates the need to heat or cool the mixture significantly from the normally prevailing ambient temperature. However, where applicable, the temperature of the mixture formed from the respective parts of the two-part (2K) composition can be raised to above the mixing temperature and / or application temperature using conventional means (including microwave induction).

[0253] The present invention will be described with reference to the accompanying drawings, in which:

[0254] Figure 1a A bonded structure according to a first embodiment of the invention is shown.

[0255] Figure 1b A bonded structure according to a second embodiment of the invention is shown.

[0256] Figure 2a The initial debonding of the structure of the first embodiment is shown when an electric current is passed through the structure.

[0257] Figure 2b The initial debonding of the structure of the second embodiment is shown when an electric current is passed through the structure.

[0258] As attached Figure 1aAs shown in , a bonded structure is provided, wherein a cured adhesive layer (10) is disposed between two conductive substrates (11). A non-conductive material layer (12) may be disposed on the conductive substrate (11) to form a bonded structure as shown in Figure 1b . Each layer of the conductive substrate (11) is in electrical contact with a power source (13), which may be a battery or an AC-driven direct current (DC) source. The positive and negative terminals of the power source (13) are shown in a fixed position, but those skilled in the art will of course recognize that the polarity of the system can be reversed.

[0259] Two conductive substrates (11) are shown in the form of layers, which may consist in particular of: a metal film; a metal sheet; a metal mesh or grid; deposited metal particles; a resin material, which is made conductive by a conductive element disposed therein; or a conductive oxide layer. As exemplary conductive elements, silver filaments, single-walled carbon nanotubes and multi-walled carbon nanotubes may be mentioned. As exemplary conductive oxides, doped indium oxides, such as indium tin oxide (ITO); doped zinc oxide; antimony tin oxide; cadmium stannate; and zinc stannate may be mentioned. In addition to the choice of conductive material, a person skilled in the art will recognize that in the case where the conductive substrate (11) is in the form of a grid or mesh, which provides limited contact with the cured adhesive layer (10), the effectiveness of the debonding operation may be reduced.

[0260] When a voltage is applied between each conductive substrate (11), current is supplied to the adhesive composition (10) disposed therebetween. This initiates an electrochemical reaction at the interface of the substrate (11) and the adhesive composition, which should be understood to be oxidative at the positively charged interface or anodic interface and reductive at the negatively charged interface or cathodic interface. This reaction is believed to weaken the adhesive bond between the substrates, thereby allowing the debondable composition to be easily removed from the substrates.

[0261] like Figure 2a and Figure 2b As shown in , debonding occurs at the positive electrode interface, i.e., the interface between the binder composition (10) and the conductive surface (11) in electrical contact with the positive electrode. The binder bond at the interface of the two substrates can be weakened by reversing the direction of the current flow before separating the substrates.

[0262] However, it should be noted that the composition of the adhesive layer (10) can be adjusted so that debonding occurs at the positive electrode interface or the negative electrode interface or from both simultaneously. For some embodiments, the voltage applied across the two surfaces to form the anode interface and the cathode interface will cause debonding to occur simultaneously at the anode and cathode adhesive / substrate interfaces. In an alternative embodiment, if the composition is not responsive to direct current at both interfaces, the reversed polarity can be used to debond the two substrate / adhesive interfaces simultaneously. The current can be applied with any suitable waveform, provided that the debonding is allowed to proceed for a sufficient total time at each polarity. In this regard, sinusoidal waveforms, rectangular waveforms, and triangular waveforms may be suitable and may be applied by a controlled voltage source or a controlled current source.

[0263] Without intending to limit the invention, it is believed that the debonding operation can be effectively performed when at least one and preferably two of the following conditions occur: a) an applied voltage of 0.5-100V; and b) the voltage is applied for a duration of 1 second to 60 minutes. In the case of promoting the release of the conductive substrate from the cured adhesive by applying a force (e.g., via a weight or spring), the potential may only need to be applied for about a few seconds. In some embodiments, a potential of 5V for 10 minutes is sufficient to have a debonding effect.

[0264] Desirably, after debonding, the adhesive composition is only on the first substrate or the second substrate, meaning that one of the substrates is substantially free of adhesive.

[0265] The following examples illustrate the invention but are not intended to limit the scope of the invention in any way.

[0266] Example

[0267] The following materials are used in the examples:

[0268] 1-Butyl-3-methylimidazolium bis(trifluoromethyl) was obtained from Sigma Aldrich.

[0269] Sulfonyl)imide:

[0270] 1-Dodecyl-3-methylimidazolium bis(trifluoro)benzene was obtained from Sigma Aldrich.

[0271] Methylsulfonyl)imide:

[0272] Trihexyltetradecylphosphonium bis(trifluoromethylsulfonium) was obtained from Sigma Aldrich

[0273] Acyl)amide:

[0274] Cyphos IL 109: Available from Solvay.

[0275] Methyl methacrylate: Available from Sigma Aldrich.

[0276] Methacrylic acid: Available from Acros Organics.

[0277] 2-Hydroxyethyl methacrylate phosphate: Available from Sigma Aldrich.

[0278] 2,2'-(4-Methylphenylimino)diethanol: Available from Sigma Aldrich.

[0279] Garamite 1958: Powdered rheological additive based on organophilic layered silicates, available from BYK.

[0280] Aerosil 200: Hydrophilic fumed silica available from Evonik Industries.

[0281] Zinc oxide nanopowder: Available from Sigma Aldrich.

[0282] Kraton D 1155ES: Linear block copolymer based on styrene and butadiene with 40% by mass of bound styrene, available from Kraton Corporation.

[0283] Kurarity LA4285: An all-acrylic block copolymer (MAM) available from Kuraray Co. Ltd.

[0284] Nipol 1472X: Acrylonitrile butadiene rubber available from Zeon Chemicals.

[0285] Hypro 2000X168 LC VTB: Methacrylate terminated polybutadiene rubber available from Huntsman.

[0286] Blendex 338: Ultra high rubber acrylonitrile butadiene rubber (ABS) resin available from Galata Chemicals.

[0287] Pluracol V10: a copolymer ether of ethylene oxide-propylene oxide and trimethylolpropane (CAS No. 52624-57-4), available from BASF SE.

[0288] Benzoflex 2088: A blend of diethylene glycol benzoate, dipropylene glycol benzoate, and triethylene glycol benzoate available from Eastman Chemical Company.

[0289] Triphenylphosphine: Available from Merck KGaA

[0290] Wax component: Paraffin wax, available from International Group Inc.

[0291] Ferrocene: Available from Merck.

[0292] DER 331: Bisphenol A epoxy resin available from Olin Corporation.

[0293] Benzoyl peroxide (75%): Powder, available from Arkema Inc.

[0294] The following test methods have been used to characterize two-part formulations:

[0295] Tensile Lap Shear (TLS) Testing :The substrates tested were nickel (thickness 1.5 mm), aluminum (AA6016, thickness 1.25 mm) and stainless steel (1.4301, thickness 1.5 mm). The substrates were cut into a size of 2.5 cm × 10 cm for tensile testing. Based on the determination of tensile lap shear strength of EN 1465:2009 (German version) adhesive-bonded assemblies, tensile lap shear (TLS) tests were performed at room temperature. The bonding overlap area of ​​each of the substrates was 2.5 cm × 1.0 cm (1 "× 1"), where the bonding thickness was 150 μm. The applied two-component (2K) adhesive composition was cured at 80 ° C for 30 minutes in the overlapping area. The test specimen was placed in the fixture of a universal testing machine and pulled at 10 mm / min until failure occurred. The fixtures for fixing the ends of the assembly must be aligned so that the applied force is applied through the center line of the specimen. The type of failure can be adhesive (where the adhesive separates from one of the substrates) or cohesive (where the adhesive breaks within itself).

[0296] Aging test:The substrates tested were aluminum (AA6016, thickness 1.25 mm) and stainless steel (1.4301, thickness 1.5 mm). The substrates were cut into a size of 2.5 cm × 10 cm for tensile testing. The bonding overlap area of ​​each substrate was 2.5 cm × 1.0 cm, wherein the bonding thickness was 150 μm. The applied two-component (2K) adhesive composition was cured for 20 minutes at 45 ° C (Example 1) or 80 ° C (Example 2) in the overlapping area. The specimens were stored in a climate chamber at 90% relative humidity and 65 ° C: At the specified time in storage (1 day, 7 days, 14 days and 21 days), a tensile lap shear (TLS) test was performed at room temperature according to the above method (EN 1465:2009, German version). The test specimen was placed in the fixture of a universal testing machine and pulled at 10 mm / min until failure occurred.

[0297] Thin Bond Line Test :The substrate tested is stainless steel (1.4301, thickness 1.5mm). The substrate is cut into a size of 2.5cm×10cm for tensile testing. The bonding overlap area of ​​each substrate is 2.5cm×0.25cm, wherein the bonding thickness is 150μm. The applied two-component (2K) adhesive composition is cured at 80°C for 20 minutes in the overlapping area. Tensile lap shear (TLS) test is performed at room temperature according to the above method (EN 1465:2009, German version). The test specimen is placed in the fixture of a universal testing machine and pulled at 10mm / min until failure occurs.

[0298] T-Peel Resistance (N / mm):The test of this parameter is based on the following standards: ASTM D1876 Peel Resistance of Adhesives; ISO 11339 Adhesives - 180° Peel Test for Flexible-to-Flexible Bonded Assemblies; DIN 53282 Testing of Adhesives for Metals and Adhesively Bonded Metal Joints. For each test point, at least three test specimens are assembled and tested. The bond is prepared using an aluminum peeling substrate that has been wiped with acetic acid to remove dirt or grease from it. The composition to be evaluated is applied to both sides of the peeling strip specimen. Starting with one end, the composition is spread with an applicator rod to ensure a coverage area of ​​25×50 mm. Then, the second peeling strip specimen is matched with the coated peeling strip specimen. The resulting assembly was clamped using one clamp on each side of the assembly and one clamp at the end of the assembly (three clamps total) to ensure that the clamping load was evenly distributed. The composition was then cured within the assembly at 80°C for 20 minutes. The clamps were removed after 24 hours and the bond was pulled to provide a T-peel result.

[0299] Impact strength(N / mm): The test of this parameter is based on the following standard: ASTM 3762 Standard Test Method for Adhesive-Bonded Surface Durability of Aluminum (Wedge Test). In this test, aluminum specimens are prepared according to ASTM D1002. According to these standards, a pendulum impact tester is used, which is equipped with a retaining bolt, an active strain gauge and a hammer fin, and is also equipped with an instrument for determining force-time curves and force-deflection curves. For each specimen, the applied two-component (2K) adhesive composition is cured at 80°C for 20 minutes in the overlapping area. The specimen is inserted into a wedge test fixture, wherein the unbonded end protrudes enough to allow the wedge to be inserted between the adherends. The test fixture is then assembled into the specimen retaining bolt, which is first hand-tightened and then tightened an additional quarter turn using a suitable tool. The specimen is then allowed to stabilize at 25°C and 50% relative humidity before the shock is applied, for which 2.3ms is specified. -1 During the impact event, the sensor signal is automatically and non-selectively detected and recorded by the microprocessor; the force-time (or force-displacement) data is then processed separately.

[0300] Membrane properties : The modulus (MPa), elongation at break and tensile strength (MPa) of the adhesive film were tested according to ASTM D638-14 Standard Test Method for Tensile Properties of Plastics. An adhesive film with a thickness of 2.3 mm was prepared by curing the two-component (2K) adhesive composition at 80° C. for 20 minutes.

[0301] Viscosity : Measurement of exemplary compositions at 20 s- 1 performed at a shear rate of .

[0302] The (B) part of the two-component composition of each composition 1 to 6 was prepared according to the following Table 1 herein:

[0303] Table 1

[0304]

[0305] Example 1

[0306] Part (A) of Composition 1 of Example 1 was prepared according to Table 2 herein below.

[0307] Table 2

[0308]

[0309] The parts were loaded into separate compartments of a 50 g cartridge at a weight ratio of 10:1 (A:B) and sealed at both ends. The cartridge was then loaded into a cartridge-gun and a mixing tip was installed at the front end. The two parts were pushed into the mixing tip by applying constant pressure on the trigger to ensure thorough mixing before application to the substrate.

[0310] For each substrate, tensile lap shear strength test, aging test, peel strength test, wedge impact test and film property test were performed as above. The applied two-part (2K) adhesive composition was cured in the overlap area by applying the temperature conditions described for each test. Where applicable, the samples were stored in a climate chamber prior to testing.

[0311] The results are reported in Table 3 herein below.

[0312] Table 3

[0313]

[0314] For adhesive bonded stainless steel substrates, lap shear strength (MPa) was investigated under the debonding conditions provided below in Table 4, specifically with and without application of an electrical potential across the bond area. Where applicable, aged specimens were stored in a climate chamber at 90% relative humidity and 65°C; and a constant electrical potential (30 V) was applied across the overlapped bond area for a period of 20 minutes.

[0315] Table 4

[0316] Aging (hours) Adhesion strength (MPa) 30V, Adhesion Strength after 20 minutes (MPa) 0 21.84(±1.00) 4.74(±1.70) 48 19.73(±1.50) 4.17(±0.50)

[0317] Example 2

[0318] Part (A) of the composition of Example 2 was prepared according to Table 5 herein below.

[0319] Table 5

[0320]

[0321] The parts were loaded into separate compartments of a 50 g cartridge at a weight ratio of 10:1 (A:B) and sealed at both ends. The cartridge was then loaded into a cartridge gun and a mixing tip was installed at the front end. The two parts were pushed into the mixing tip by applying constant pressure on the trigger to ensure thorough mixing before application to the substrate.

[0322] For each substrate, tensile lap shear strength test, aging test, peel strength test, wedge impact test and film property test were performed as above. The applied two-part (2K) adhesive composition was cured in the overlap area by applying the temperature conditions described for each test. Where applicable, the samples were stored in a climate chamber prior to testing.

[0323] The test results for Composition 2 are reported in Table 6 below.

[0324] Table 6

[0325]

[0326] The test results for Composition 3 are reported in Table 7 below.

[0327] Table 7

[0328]

[0329] The test results for Composition 4 are reported in Table 8 below.

[0330] Table 8

[0331]

[0332] The test results for Composition 5 are reported in Table 9 below.

[0333] Table 9

[0334]

[0335] The test results for Composition 6 are reported in Table 10 below.

[0336] Table 10

[0337]

[0338] Example 3

[0339] Compositions 7, 8 and 9 of Example 4 were prepared according to Table 11 herein below.

[0340] Table 11

[0341]

[0342] First, prepare the separate A part of the adhesive by adding all ingredients in a single kettle and stirring it overnight to dissolve all ingredients. The final adhesive is obtained by adding separate Part A and Part B separately in a 10:1 ratio and speed mixing it at 3000 rpm for 15 seconds.

[0343] The application substrate of the composition was stainless steel (EN 1.4301) and was cut into pieces of 2.5 cm x 10 cm size and 1.50 mm thickness. In order to control the thickness of the coating composition applied between the two substrates, glass beads were used as spacers with a diameter of 100-200 μm. Tensile lap shear (TLS) tests were performed at room temperature based on EN 1465:2009 (German version) Determination of tensile lap shear strength of adhesive-bonded assemblies.

[0344] The bond overlap area of ​​each substrate was 2.5 cm x 1.0 cm, with a bond thickness of 0.1 cm (40 mils). The applied adhesive composition was cured in the overlap area by first leaving it at ambient conditions for 1 hour and then applying a temperature of 80° C. for 30 minutes. The bonded structures were then stored at room temperature for 24 hours before an initial tensile test or stored in a climate chamber at 65° C. and 90% relative humidity for accelerated aging studies.

[0345] After the 24 hour storage period, tensile lap shear strength values ​​were collected before and after applying a 50V constant potential across the adhesive layer for a duration of 30 minutes, and after storage in a climate chamber at 65°C and 90% relative humidity. The results are reported in Table 12 herein below.

[0346] Table 12

[0347]

[0348] Table 12 summarizes the results obtained for different ionic liquids (BMIM NTf2, DDMIM NTf2 and Cyphos IL 109), and all compositions 7-9 show good stability after storage for 3 weeks at 65°C and 90% relative humidity, but the best is composition 9 containing Cyphons IL 109. The electrochemical delamination performance is different. DDMIMNTf2 in composition 9 shows the best overall delamination performance. BMIM NTf2 shows a poor initial delamination process, but still shows a decrease of more than 50% compared to the same system with MMA as acrylic monomer. After storage at 65°C and 90% relative humidity, unexpectedly, after 1 week, the delamination becomes worse, but after 3 weeks the delamination is greatly improved. On the other hand, Cyphos IL 109 shows the opposite behavior, with very good delamination initially, but becomes worse after storage for 3 weeks at 65°C and 90% relative humidity.

[0349] Example 4

[0350] Compositions 10-13 of Example 5 were prepared according to Table 13 herein below. R1 is a reference composition.

[0351] Table 13

[0352]

[0353] Starting from the good performance of Example 4 composition 9, the composition was repeated by varying the amount of ionic liquid Cyphos IL 109 (0, 4.26, 6.25, 8.16 and 10 wt %). First, the separate A part of the adhesive was prepared by adding all ingredients in a single kettle and stirring it overnight to dissolve all ingredients. The final adhesive was obtained by adding the separate A and B parts separately in a 10:1 ratio and rapidly mixing them at 3000 rpm for 15 seconds.

[0354] The application substrate of the formulation was stainless steel (EN 1.4301) and was cut into pieces of 2.5 cm x 10 cm size and 1.50 mm thickness. In order to control the thickness of the coating composition applied between the two substrates, glass beads were used as spacers with a diameter of 100-200 μm. Tensile lap shear (TLS) tests were performed at room temperature based on EN 1465:2009 (German version) Determination of tensile lap shear strength of adhesive-bonded assemblies.

[0355] The bond overlap area of ​​each substrate was 2.5 cm x 1.0 cm, with an adhesive thickness of 0.1 cm (40 mils). The applied adhesive composition was cured in the overlap area by first leaving it at ambient conditions for 1 hour and then applying a temperature of 80° C. for 30 minutes. The bonded structures were then stored at room temperature for 24 hours before an initial tensile test or stored in a climate chamber at 65° C. and 90% relative humidity for accelerated aging studies.

[0356] After the 24 hour storage period, tensile lap shear strength values ​​were collected before and after application of a 50V constant potential across the adhesive layer for a duration of 30 minutes, and after storage in a climate chamber at 65°C and 90% relative humidity. The results are reported in Table 14 herein below.

[0357] Table 14

[0358]

[0359] After 1 week storage at 65°C and 90% relative humidity, reference composition R1 shows a significant increase in lap shear strength values, but overall, after 3 weeks storage at 65°C and 90% relative humidity, we only observe a slight increase in the initial lap shear strength.

[0360] As the Cyphos IL 109 content increases, we observe a gradual decrease in the initial lap shear strength (from more than 20 MPa (composition 10) to 15 MPa (composition 13)). In all compositions, we also observe an increase in the lap shear strength after storage for 1 week at 65°C and 90% relative humidity, but this increase becomes smaller as the Cyphos IL 109 content increases. Finally, all compositions also show a subsequent decrease in lap shear strength after storage for 3 weeks at 65°C and 90% relative humidity. Overall, the decrease in lap shear strength after storage for 3 weeks at 65°C and 90% relative humidity is small compared to the initial values, which means that all compositions are very stable after storage at 65°C and 90% relative humidity. Finally, the electrochemical delamination performance is the worst for composition 10 with 4.26 wt% Cyphos IL 109. However, the decrease in lap shear strength is still above 50%, which is much better than the system using MMA as acrylic monomer. Cyphos IL 109 contents above 4.26 wt% show excellent delamination properties, but after storage at 65°C and 90% relative humidity a degradation of the properties is observed, but the final delamination performance is still above 50% and thus much better than the system using MMA as acrylic monomer.

[0361] In view of the foregoing description and examples, it will be apparent to those skilled in the art that equivalent modifications may be made without departing from the scope of the appended claims.

Claims

1. A curable and debondable two-part adhesive composition, the curable and debondable two-part adhesive composition comprising: The first part (A), wherein the first part (A) comprises: (Meth)acrylate monomers; Copolymerizable acids; and Electrolytes; and The second part (B), wherein the second part (B) comprises: a first curing agent for the monomers of the first portion; a second curing agent for the monomers of the first portion; wax; and Solubilizer, wherein the two-part (2K) adhesive composition further comprises: Toughening agent; Oxygen scavengers; and Rheology control agents; Further wherein the two-part (2K) adhesive composition is characterized in that the electrolyte comprises or consists of at least one salt according to formula (I) or formula (II): in: R 1 , R 2 , R 3 , R 4 and R 5 independently selected from hydrogen, C1-C 18 Alkyl, C3-C 18 Cycloalkyl, C6-C 18 Aryl, C7-C 24 Aralkyl, C2-C 20 Alkenyl, -C(O)R q , -C(O)OH, -CN, or -NO2; and R q C1-C6 Alkyl; and X - is a counter anion selected from the group consisting of: The formula R a Japanese R b independently selected from hydrogen, C1-C 12 Alkyl, C5-C 12 Cycloalkyl, C5-C 12 Heterocycloalkyl, C6-C 18 Aryl, or C5-C 18 Heteroaryl.

2. The curable and debondable two-part adhesive composition according to claim 1, wherein the (meth)acrylate monomer is selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, esters, phenyl (meth)acrylate, toluene (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, octadecyl (meth)acrylate, glycidyl (meth)acrylate, isobornyl (meth)acrylate, 2-aminoethyl (meth)acrylate, γ-(meth)acryloyloxypropyltrimethoxysilane, (meth)acrylic acid-ethylene oxide adduct, trifluoromethyl methyl (meth)acrylate, 2-trifluoromethylethyl (meth)acrylate, 2-perfluoroethyl (meth)acrylate 2-Perfluoroethyl-2-perfluorobutylethyl (meth)acrylate, 2-Perfluoroethyl (meth)acrylate, Perfluoromethyl (meth)acrylate, Diperfluoromethyl methyl (meth)acrylate, 2-Perfluoromethyl-2-perfluoroethyl methyl (meth)acrylate, 2-Perfluorohexylethyl (meth)acrylate, 2-Perfluorodecylethyl (meth)acrylate, 2-Perfluorohexadecylethyl (meth)acrylate, Ethoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, dipentaerythritol monohydroxypentaacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol di acrylate, neopentyl glycol diacrylate, pentaerythritol tetraacrylate, 1,2-butylene glycol diacrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated tri(meth)acrylate glycerol, trimethylolpropane tri(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, tripropylene glycol di(meth)acrylate, propoxylated neopentyl glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, and mixtures thereof, Preferably, the (meth)acrylate monomer is selected from methyl methacrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, isobornyl methacrylate, isobornyl acrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, and mixtures thereof.

3. A curable and debondable two-part adhesive composition according to claim 1 or claim 2, wherein the (meth)acrylate monomer component is present in an amount of 20-80 wt%, preferably 30-60 wt%, more preferably 35-50 wt%, based on the total weight of the first part.

4. The curable and debondable two-part adhesive composition according to any one of claims 1 to 3, wherein the copolymerizable acid is selected from methacrylic acid, acrylic acid, itaconic acid, maleic acid, aconitic acid, crotonic acid, fumaric acid, and mixtures thereof, wherein preferably the copolymerizable acid is methacrylic acid.

5. A curable and debondable two-part adhesive composition according to any one of claims 1 to 4, wherein the copolymerizable acid is present in an amount of 0.5-20 wt%, preferably 5-15 wt%, more preferably 6-12 wt%, based on the total weight of the first part.

6. A curable and debondable two-part adhesive composition according to any one of claims 1 to 5, wherein the electrolyte is selected from: 1-methylimidazolium bis(trifluoromethylsulfonyl)imide; 3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-butyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide; 1-hexyl-3-methylimidazolium Bis(trifluoromethylsulfonyl)imide; 1-octyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-methyl-3-octylimidazolium bis(trifluoromethylsulfonyl)imide; 1-decyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; tetraethylphosphonium bis(trifluoromethylsulfonyl)imide; tetrabutylphosphonium bis(trifluoromethylsulfonyl)imide; tridecyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide; trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl)amide; and mixtures thereof, Preferably, it is selected from 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl)amide, and mixtures thereof.

7. A curable and debondable two-part adhesive composition according to any one of claims 1 to 6, wherein the electrolyte is present in an amount of 0.5-20 wt%, preferably 5-15 wt%, more preferably 6-12 wt%, based on the total weight of the first part.

8. A curable and debondable two-part adhesive composition according to any one of claims 1 to 7, wherein the first curing agent is a peroxide curing agent, The peroxide curing agent is preferably selected from tert-butyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, tert-butyl perbenzoate, diacetyl peroxide, benzoyl peroxide, tert-butyl peracetate, lauryl peroxide, and mixtures thereof. The peroxide curing agent is more preferably benzoyl peroxide.

9. The curable and debondable two-part adhesive composition of any one of claims 1 to 8, wherein the first curing agent is present in an amount of 5-40 wt% of the total weight of the second part.

10. A curable and debondable two-part adhesive composition according to any one of claims 1 to 9, wherein the second curing agent is a metal compound selected from the group consisting of salts and coordination compounds of iron, copper, cobalt, vanadium and manganese, The second curing agent is preferably an iron-based compound selected from ferrocene, iron (II) acetylacetonate, ammonium ferrocyanide, and mixtures thereof.

11. A curable and debondable two-part adhesive composition according to any one of claims 1 to 10, wherein the second curing agent is present in an amount of 0.01-2 wt%, preferably 0.01-1 wt%, more preferably 0.01-0.5 wt%, based on the total weight of the second part.

12. A curable and debondable two-part adhesive composition according to any one of claims 1 to 11, wherein the solubilizing agent is polyethylene glycol or an epoxy resin selected from the group consisting of cycloaliphatic epoxy compounds, epoxy novolac resins, bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol A epichlorohydrin-based epoxy resins, alkyl epoxy compounds, limonene dioxide, polyepoxides, and mixtures thereof, Preferably, the solubilizing agent is bisphenol A epoxy resin.

13. A curable and debondable two-part adhesive composition according to any one of claims 1 to 12, wherein the solubilizer is present in an amount of 20-60 wt%, preferably 30-60 wt%, more preferably 40-60 wt%, based on the total weight of the second part.

14. A curable and debondable two-part adhesive composition according to any one of claims 1 to 13, wherein the toughening agent is present in an amount of 5-40 wt%, preferably 10-40 wt%, more preferably 20-40 wt%, based on the total weight of the composition.

15. A curable and debondable two-part adhesive composition according to any one of claims 1 to 14, wherein the first part (A) and the second part (B) are combined in an A:B weight ratio of 20:1 to 1:1, preferably 15:1 to 5:1, more preferably 12:1 to 8:

1.

16. A bonded structure comprising: a first material layer having a conductive surface; as well as a second material layer having a conductive surface; The cured debondable two-part adhesive composition according to any one of claims 1 to 15 is disposed between the first material layer and the second material layer.

17. A method of debonding a bonded structure according to claim 16, the method comprising the steps of: i) applying a voltage across the two surfaces to form an anodic interface and a cathodic interface; as well as ii) debonding the surface.

18. The method according to claim 17, wherein the voltage applied in step i) is 0.5-100 V and is preferably applied for a duration of 1 second to 60 minutes.

Citation Information

Patent Citations

  • Preparation of carbonates

    EP0119840A1

  • A curable composition

    EP0520426B1

  • Two component (2K) curable adhesive composition

    EP3835381A1

  • Production of alkylene carbonates

    GB1485925A

  • Electrically disbondable compositions and related methods

    US20070269659A1